La volonté des parties dans les procédures de régulation - Perez, Léa (Université de Montpellier, 2019)
L’ouverture des processus décisionnels et le développement constant de procédés négociés imprègnent la trajectoire récente des procédures de régulation, quel que soit le champ régulé. Ces mouvements sont symptomatiques de « l’évolution de la technique juridique dans les sociétés occidentales » diagnostiquée par le professeur Amselek dès le début des années quatre-vingt. Cette étude transversale des méthodes déployées par les autorités de régulation révèle toutefois l’émergence d’un couplage original entre la faculté de solliciter l’adhésion des opérateurs, par leur acquiescement ou leur participation, et la capacité de recourir spontanément à des instruments en marge de la typologie classique des actes et procédures administratifs. Les procédures de régulation laissent ainsi place à des espaces modulés par la volonté des régulateurs et des opérateurs régulés, respectivement identifiés comme parties au processus de régulation. Or l’irruption du registre volontaire au sein de relations structurellement inégalitaires entre puissance publique et acteurs privés n’est ni sans cause ni sans conséquence sur l’environnement juridique dans lequel il s’insère. Les causes sont classiques mais prennent un relief particulier dans le cadre de la régulation économique. La prédilection systématique pour les procédés ouverts au milieu régulé ou choisis par les parties est alimentée par des dynamiques et des facteurs contextuels propres au domaine étudié. Ce travail de recherche s’est attaché à en établir la topologie, en interrogeant le rôle de la volonté des parties dans les procédures de régulation. Les conséquences de l’exaltation de la capacité de choix du régulateur et du régulé sont en revanche moins explorées par la doctrine et plus délicates à systématiser. La présente étude se propose ainsi de mettre en évidence les marqueurs d’acclimatation et d’envisager les prémices d’une reconfiguration du système de régulation à travers le phénomène de compliance.
Keywords: Droit; Expression de la volonté (droit); Impact; Opérateurs; Parties; Procédure (droit); Procédures; Regulation; Regulatory procedures; Régulation; Volonté; Willingness

The Impact of Economic Institutions on Small Firms in Developing Countries - Pouliquen, Victor (Ecole des Hautes Etudes en Sciences Sociales, 2019)
In many developing countries, economic institutions are failing. This translates into structural problems such as widespread informality, rampant corruption and the impossibility for governments to raise taxes. This thesis study how economic policies affect economic institutions in developing countries. It focuses on two broad questions: (1) What are the effects of policies to reduce informality? and (2) how are new technologies reshaping the way governments collect taxes?The first chapter uses a randomized experiment to study the introduction of a new legal status in Benin, created to make it easier for small firms to become formal. To make this new status attractive, the government added supplementary incentives designed to enhance the presumed benefits of formalizing. We find that few firms register when just given information about the new regime, but our full package of supplementary efforts boosts formalization by 16.3 percentage points. However, this formalization does not bring firms higher sales, profits or access to credit, and the cost of formalizing these firms exceeds the added taxation they will pay over the next decade. We show how better targeting of these policies towards firms that look more like formal firms to begin with can increase the formalization rate and improve cost-effectiveness. The second chapter studies the impact of formalization on intra-household relationships, still in Benin. The idea behind this chapter is that formalization changes effective property rights by clarifying who in the household is the legal owner of the business and who will keep it in case of divorce. The causal effect of formalization is identified using the same random experiment used for the first chapter. We find first that formalization increases entrepreneurs' (both male and female) control over household revenue. They contribute proportionally less to household expenditures and to the personal expenses of their partner. Second, using a behavioral game, we find strong gender differential effects of formalization on the probability that entrepreneurs pay to hide a windfall transfer from their spouse. Female entrepreneurs are much more likely to pay to hide, while male entrepreneurs are much less likely to do so. Using a theoretical model, we show that this result is compatible with the idea that women entrepreneurs are constrained and cannot invest as much as they would like in their own business. Women who became formal hide the windfall transfer more because they have more property rights and want to invest more in their business. Our conclusion is that formalization has important effects on intra-household dynamics.The third and final chapter of this thesis deals with the second question and examines how internet is changing the way taxes are collected. Specifically, we study the impact of electronic tax filing (e-filing) for small firms to replace in-person submission of paper-based forms to tax officials. We examine the impact of e-filing on compliance costs, tax payments, and bribes payments using experimental variation and data from Tajikistan firms. We find that firms that e-file have lower compliance costs, spending five fewer hours each month on fulfilling tax obligations. There are no significant average effects of e-filing on tax or bribe payments, but significant heterogeneity exists across firms by their baseline likelihood of tax evasion. Among firms previously more likely to evade, e-filing doubles tax payments, likely by disrupting collusion with officials. Conversely, among firms less likely to have been evading, e-filing reduces tax payments, suggesting that officials had previously required them to pay more. These firms also pay fewer bribes, as e-filing reduces opportunity for extortion. Our conclusion is that e-filing reduces compliance costs and makes the distribution of tax payments across firms arguably more equitable. Dans les pays en développement, les institutions économiques sont souvent défaillantes. Cela se traduit par des problèmes structurels tels que l’omniprésence du secteur informel, la corruption généralisée et l’incapacité des États à collecter les impôts. Cette thèse porte sur les politiques publiques permettant d’améliorer le fonctionnement des institutions économiques. Elle se focalise sur deux questions : (1) Quels sont les effets des politiques de réduction de l’informalité ? et (2) Comment les nouvelles technologies affectent la collecte des taxes ? Le premier chapitre étudie à l’aide d’une expérimentation aléatoire l’introduction d’un statut légal facilitant la formalisation des petites entreprises au Bénin. Afin de rendre ce statut attractif le gouvernement l’a accompagné d’incitations supplémentaires créés pour amplifier les bénéfices potentiels de la formalisation. Nous trouvons que très peu d’entreprises se formalisent lorsqu’elles reçoivent uniquement de l’information sur le nouveau statut. Cependant, lorsque l’information est combinée aux incitations, la formalisation augmente de 16,3 points de pourcentage. En revanche, les effets sur les performances des entreprises sont limités, et le coût des incitations est supérieur au total des impôts qu’elles paieront pendant les 10 prochaines années. Enfin, nous montrons comment un ciblage sur les entreprises ayant des caractéristiques proches des entreprises déjà formelles améliorerait l’efficacité de ce type de programme. Le second chapitre étudie l’impact de la formalisation sur les relations intra-ménages, toujours au Bénin. Dans ce contexte, la formalisation renforce les droits de propriété et clarifie au sein des ménages qui est le propriétaire légal de l’entreprise, et qui la gardera en cas de divorce. L’effet causal de la formalisation est identifié à l’aide de l’expérimentation aléatoire déjà utilisée pour le premier chapitre. Nous trouvons que les entrepreneurs s’étant formalisés ont plus de contrôle les ressources de leur ménage. Ils ou elles contribuent proportionnellement moins aux dépenses du ménage et transfèrent moins d’argent à leur partenaire. Deuxièmement, en utilisant un jeu comportemental dans lequel les entrepreneurs peuvent cacher un transfert monétaire à leur partenaire, nous trouvons que les femmes qui se sont formalisées cachent davantage à leur mari. A l’aide d’un modèle théorique, nous montrons que ce résultat est compatible avec l’idée que les femmes ne sont pas libres d’investir comme elles le souhaiteraient dans leur entreprise et doivent le faire secrètement. Notre conclusion est que la formalisation a des effets importants sur les dynamiques intra-ménage. Le troisième chapitre utilise une expérimentation aléatoire conduite au Tadjikistan pour étudier l’impact d’un système permettant aux entreprises de déclarer leurs taxes en ligne plutôt que de soumettre un formulaire en personne. Nous trouvons que ce système réduit le temps passé par les entreprises pour remplir leurs obligations fiscales de 5 heures par mois. Nous ne trouvons pas d’effets sur le montant des impôts payés ni sur le versement de pots-de-vin. En revanche, l’absence d’effets moyens masque une importante hétérogénéité. Les entreprises le plus susceptibles de faire de l’évasion fiscale dans le système précédent payent davantage d’impôts quand elles déclarent en ligne, probablement car elles ne peuvent plus entrer en collusion avec les agents des impôts. À l'inverse, les entreprises qui étaient les moins susceptibles de faire de l’évasion, payent moins des taxes quand elles déclarent en ligne, suggérant qu’elles étaient forcées de payer plus d’impôts avant. Ces entreprises paient également moins de pots-de-vin, ce qui suggère que déclarer en ligne offre une protection contre le risque d'extorsion de la part des agents du fisc. Notre conclusion est que permettre la déclaration des taxes en ligne a rendu l’appareil fiscal à la fois plus efficace et plus juste.
Keywords: Droits de Propriétés; Electronic Tax Filing; Impôt; Impôt (recouvrement); Informality; Informalité; Innovation; Intra-Household Relationships; New Technologies; Nouvelles Technologies; Paiement en ligne des Taxes; Petites Entreprises; Petites et moyennes entreprises; Property Rights; Propriété; Relations Intra-Ménage; Small Firms; Taxation; Économie souterraine

Les partenariats public-privé dans le domaine des services énergétiques - Fall, Mamadou (Université de Bordeaux, 2019)
Secteur très particulier, le domaine des services énergétiques tire sa sensibilité des enjeux économiques et de souveraineté qu’il soulève. Cela justifie la présence accrue de la puissance publique à travers diverses formes d’intervention. Parmi celles-ci figure le partenariat public-privé qui caractérise les différentes relations qu’entretiennent les personnes publiques avec les acteurs du secteur privé pour la prise en charge des activités économiques dans des conditions compatibles avec le service de l’intérêt général. Ce mode d’intervention économique très protéiforme dans sa mise en oeuvre soulève néanmoins des interrogations sur sa pertinence et son efficacité dans la gestion des services énergétiques. Si les partenariats public-privé ont largement contribué au développement des activités énergétiques, leur cadre juridique s’avère aujourd’hui quelque peu inadapté aux enjeux actuels de ce secteur, en particulier dans un contexte de transition énergétique. Il est possible d’en faire de véritables leviers de cette dynamique de transitionnelle à la condition toutefois d’en adapter le cadre juridique afin de le rendre plus apte à concilier les impératifs économiques avec les externalités environnementales et socio-politiques inhérentes au secteur de l’énergie.
Keywords: Domaine public; Economie mixte; Energie; Energy law; Partenariat public-privé; Public contracts; Public-Private partenership; Transition énergétique; Valorisation économique; Économie mixte

Les entreprises françaises et la commande publique en Afrique - Perichon, Lukas (Université Paris-Saclay, 2019)
Les relations contractuelles entre les États africains francophones et les entreprises françaises dans la commande publique se nouent dans un cadre juridique et institutionnel constitué d'un enchevêtrement complexe de normes nationales, régionales et internationales en rupture progressive avec le modèle historique français. Ces relations se formalisent dans des contrats hybrides, aux caractères mal définis, entre contrats publics et contrats internationaux. Ils s'insèrent dans des montages juridiques et financiers où sont mis en balance la profitabilité, l'intérêt général, et les enjeux environnementaux et sociaux du développement. Contractual relationships between french-speaking african countries and french companies in the public procurement sector are formed under a complex network of national, regional and international rules breaking away from the historical french legal and administrative model. These relationships are maintained through ill-defined hybrid contracts that draw from public and international contractual laws and practices. They are integrated into legal and financial frameworks balancing profitability, public interests, environmental and social matters.
Keywords: Africa; Afrique; Afrique francophone; Commande publique; Contrats administratifs; Droit international; Droit public; International law; Marché public; Public law; Public procurement

L'entrepreneuriat en droit OHADA : analyse comparative à la lumière du système français - Touré, Lalla Aicha Oumoul Makhtoum (Université de Perpignan Via Domitia, 2019)
Cette thèse aborde le problème de l’abondance des activités dans l’économie informelle en Afrique qui échappent au contrôle et à la régulation de l’état. L’objectif est de participer par l’intermédiaire d’un débat juridique d’une dimension continentale, à l’analyse du rôle de l’entrepreneur en matière de développement économique. Dans un contexte d’évolution du droit des affaires il est particulièrement important de s’intéresser au rôle de l’entrepreneur en tant qu’acteur économique. Nous proposons une approche comparative à la lumière du droit français pour encourager la création d’entreprise dans les états de l’Afrique de l’ouest. Dans cette optique le législateur OHADA intervient en vue de mettre en place une réglementation simplifiée permettant aux particuliers de se lancer dans la vie des affaires, sans se soumettre à des contraintes sévères de légalité. L’intégration de l’Entrepreneuriat par le biais de la révision de l’acte uniforme sur le droit des sociétés et groupement d’intérêt économique du 31 janvier 2014, l’acte uniforme sur le droit commercial général du 15 décembre 2010, l’acte uniforme relatif au droit des sociétés coopératives du 15 décembre 2010, constitue un levier fondamental. Une nouvelle réglementation est désormais attribuée à des professionnels qui n’étaient pas régit par le droit commercial. Cette innovation majeure traduit cette volonté de faire participer l’ensemble des citoyens au développement économique. L’objet de la présente étude est d’analyser les avantages et les inconvénients de cette facilité de gestion qu’offre l’entrepreneuriat en droit de l’OHADA à travers une vision d’ensemble des actes uniformes intéressant la création d’entreprise. Nous discutons enfin de la pertinence de cette approche par une mise en parallèle avec le modèle français très avancé en matière d’entrepreneuriat. A travers l’importance accordée au micro crédit, à la diversification des modes de financement, au secteur formel, mais aussi et surtout au changement de statut. L’entreprenant en droit OHADA présente d’énormes similitudes avec le statut d’auto- entrepreneur résultant d’une innovation de la législation française par la loi de modernisation du 04 août 2008. De plus, des transitions peuvent être envisagées, à travers la création de société commerciale. En effet, la France offre une large gamme de modes transitoires allant de l’auto entrepreneur, l’entreprise individuelle, l’entreprise unipersonnelle à responsabilité limitée à la création de société commerciale. Il sera également question de souligner le caractère superficiel de certains aspects du statut juridique de l’entreprenant. Le champ d’application des règles régissant ce statut est souvent limité, car le législateur laisse le soin aux états membres de décider sur certains points. C’est sans doute ce qui est à l’origine de cette absence de conciliation des logiques nationales au dynamisme communautaire. La notion d’entreprenant suscite alors de nombreuses incertitudes, une synthèse de solutions pourrait favoriser le maintien de ce statut. La formalisation de l’informel constitue aujourd’hui un phénomène complexe, mais essentiel pour faire face à la faible croissance des économies africaines. L’auto-entrepreneuriat est généralement considéré en France comme source de complément de revenu, alors qu’en Afrique elle représente une part importante de l’économie de subsistance.
Keywords: Acte uniforme; Company; Droit des affaires; Entrepreneuriat; Entrepreneurship; Informal sector; Pays de l'OHADA; Reforms; Réformes; Secteur informel; Société; Uniform acts; Économie souterraine

O design da ruptura dos contratos empresariais de prazo determinado - Butruce, Vitor Augusto José (Universidade de São Paulo, 2019)
A tese procura analisar o problema da aplicação dos mecanismos de ruptura dos contratos empresariais de prazo determinado e lhes propor uma nova semântica, à luz da observação da práxis e sob as premissas da teoria do design contratual. Trata-se de trabalho de teoria jurídica destinado a propor soluções dogmáticas. Ela analisa a ruptura contratual, consistente no progressivo esgarçamento da relação entre as partes, motivado por frustrações com a performance da operação ou pelo desejo de abandoná-la em prol de outros investimentos, que tende a resultar no seu encerramento antecipado. O Capítulo 1 delimita o objeto de análise e o Capítulo 2 descreve a ruptura como um processo planejado, que repercute no plano da eficácia, iniciado durante a redação contratual, quando se vislumbram diferentes cenários do porvir e se escolhem alternativas para permitir saídas eficientes e evitar posturas oportunistas em cenários de inadimplemento, desalinhamento ou mudanças de planos. O estudo constata que esse planejamento nem sempre é frutífero, sobretudo porque nossa cultura jurídica ainda desconhece suas feições e por incompatibilidades entre o raciocínio dos redatores contratuais e características próprias do Direito brasileiro. A tese propõe se adotar a teoria do design contratual para oferecer uma nova semântica à dogmática desses contratos, descrevendo-o como o conjunto de escolhas efetuadas para moldar os contratos de modo funcional, adotando-se estruturas que visam a atender aos objetivos e necessidades das partes, pressupondo antever cenários de disputas e traçar alternativas de modo estratégico, para que os investimentos em custos de transação sejam eficientes e evitem o oportunismo. O trabalho demonstra que isso se faz mediante dois raciocínios: alternando-se entre mecanismos de enforcement jurídico ou relacional para enfrentar contingências, e alternando-se entre investimentos em custos de transação ex ante ou ex post no grau de detalhamento dos parâmetros contratuais, com a adoção combinada de regras ou standards. Partindo disso, o texto identifica os elementos que integram a intenção contratual: os meios estruturais e os fins contratuais. Em seguida, demonstra que as partes efetuam escolhas sobre os meios estruturais mais adequados para atingir os fins contratuais, e que o julgador deve respeitá- las, atuando em espaços delimitados de discricionariedade. O Capítulo 3 analisa o modo como o processo de ruptura contratual ocorre, do seu planejamento até sua eclosão. Os Capítulos 4 e 5 estudam os mecanismos destinados a guiá-lo, com os olhos postos em como os redatores adaptam instrumentos típicos para tanto. Distinguem esses mecanismos pela sua função defensiva (a recusa ao cumprimento das obrigações, a retenção e a compensação convencionais), extintiva (o desligamento contratual) ou substitutiva (a contratação substitutiva e o mandato irrevogável). Em seguida, o Capítulo 6 descreve alternativas que a práxis desenvolve para lidar com riscos derivados da estrutura potestativa e do exercício unilateral daqueles mecanismos: as cláusulas escalonadas, as opções, a participação de terceiros e os step-in rights. Por fim, o Capítulo 7 antecipa pautas derivadas da incorporação dessa teoria, notadamente as irritações jurídicas relativas aos limites que doutrina e jurisprudência impõem aos mecanismos de ruptura e as possibilidades oferecidas pelas convenções processuais.
Keywords: Commercial contracts; Contract design; Contract termination; Contractual intent; Contractual rupture; Contratos empresariais; Design contratual; Desligamento contratual; Endgame provisions; Intenção contratual; Mecanismos de ruptura contratual; Ruptura contratual

Análise das relações contratuais fáticas à luz do direito de empresa - Mendes, Emerson Soares (Universidade de São Paulo, 2019)
A presente tese possui como tema central a análise da teoria da relação contratual de fato sob a visão do Direito de Empresa. Iniciando com a apresentação das bases da teoria da relação contratual de fato proposta por Günter Haupt, bem como do desenvolvimento da referida teoria por Karl Larenz, prossegue-se com a análise dos elementos estruturais do negócio jurídico e após do contrato comercial no Direito de Empresa Brasileiro, fazendo-se, ainda, uma análise do mesmo na Experiência Jurídica Romana, no Direito Inglês e no Direito Alemão. Posteriormente, segue uma análise da distinção entre contrato, relação contratual e instrumento contratual, para, então, analisar-se a natureza da responsabilidade civil pré- contatual em confronto com as relações contratuais de fato decorrentes do denominado contato social, a denominada sociedade de fato (atualmente denominada de sociedade em comum) como espécie de relação contratual de fato decorrente da inserção em uma relação comunitária, findando com o estudo do comportamento concludente como meio exteriorizador da vontade negocial na contratação da prestação de serviços públicos em confronto com a denominada relação contratual de fato decorrente da obrigação social de prestar imputada à Administração Pública.
Keywords: Common company; Comportamento concludente; Conclusive behavior; Contract; Contractual relationship; Contrat; Contrato; Pre-contractual liability; Relation contractuelle; Relação contratual; Responsabilidade pré-contratual; Responsabilité précontractuelle; Sociedade em comum

Relecture critique du Contrat de construction de maison individuelle - Baron, Irwin (Université de Nantes, 2019)
Le Contrat de construction de maison individuelle, institué par la loi 90-1129 du 19 décembre 1990, soulève de nombreuses questions. La pratique professionnelle de ce contrat de louage d’ouvrage particulier et les solutions prétoriennes mettent en relief les insuffisances et incohérences législatives. Après plus de 20 années d’existence dudit contrat, la thèse aura pour objet de procéder à sa relecture afin, tout d’abord, de constater ses défaillances menaçant l’ensemble des protagonistes du projet de construction (maître d’ouvrage, constructeur, banquier, commune, etc.). Elle révèlera les pratiques qui dénaturent le contrat, les obligations qui handicapent les parties, les risques inévitables qui affectent le projet, les jugements qui hésitent ou s’égarent, et en général, toutes les situations qui provoquent une instabilité juridique. Elle poursuivra sa démarche en se faisant force de propositions, sous un double aspect. Il lui appartiendra premièrement de suggérer des montages ou des clauses conférant plus de sécurité juridique au système existant. Elle s’efforcera secondement d’interpeller le législateur en exposant de possibles évolutions de nature à mettre fin aux confrontations de normes ou au flou légal concernant chaque année plusieurs dizaines de milliers de programmes immobiliers, le plus souvent destinés aux particuliers.Cette relecture apportera une vision neuve et à jour des problématiques légales liées à la construction de maisons individuelles depuis l’initiation du projet jusqu’à l’exécution du contrat dans des objectifs d’efficacité du droit et d’intérêt général. The contract of construction of an individual house, established by Law 90-1129 dated December 19th, 1990, raises several questions. The professional practice of this particular rental contract and the praetorian solutions accentuate the legislative insufficiencies and incoherencies. After more than 20 years of existence of said contract, the thesis will have for objective to review it in order to notice its failures which threaten all protagonists of the construction project (project manager, constructor, banker, district, etc...). It will reveal the practices that alter the contract, the obligations that handicap the parties, the inevitable risks that affect the project, the judgments that hesitate or get lost and generally all situations which cause a legal instability. It will go on with its approach by making proposals, under a double aspect. It will be up to it first to suggest setups or clauses conferring more legal safety to the existing system. Secondly, it will endeavor to question the legislator by exposing possible evolutions that are likely to put an end to the standards confrontation or to the legal limbo that concern, each year, tens of thousands of real estate programs, most often meant for individuals. This review will bring a new and up-to-date vision of the legal issues related to the construction of individual houses, from the initiation of the project until the execution of the contract, within objectives of effectiveness of the law and public interest.
Issue: 2019NANT3003
Keywords: Droit privé; Immobilier; Louage d'ouvrage; Rental contract

Rationality and legality of non-market economy treatment in Antidumping law: novel perspectives on the changed legal environment - Long, Shao (Universität Wien, 2019)
AD Recht ermöglicht die Anwendung des Instruments nichtmarktwirtschaftlicher Behandlung (NME) zwecks Bestimmung des normalen Ausfuhrpreises von importierten Waren aus Ländern deren Märkte als weitgehen von Regierungen beeinflusst und deren Preise und Kosten für diese Berechnung als unverlässlich angesehen werden. Stattdessen sollten diese Berechnungen auf der Basis von Preisen in einem Vergleichsland mit funktionierender Marktwirtschaft ( „surrogate country‟ ) erfolgen. Die vorliegende Dissertation legt dar, dass die Anwendung der NME Behandlung zum Schutz gegen unfairen Importwettbewerb nicht auf rechtlich gesicherter Grundlage erfolgt, sondern als willkürlich eingeseztes protektionistisches Instrument gehandhabt wird. Besonders die Anwendung dieser Methode auf Chinesische Exporte nach 2016 ist rechtlich fragwürdig. Die Dissertation untersucht die Rechtmäßigkeit und Zweckmäßigkeit diese Methode, erstens durch die Analyse der wirtschaftlichen Begründung des AD Rechts und der geschichtlichen Entwicklung seit seinen protektionistisch motivierten Anfängen. Sie untersucht sowohl die relevanten Regeln und Praktiken aus der Zeit vor der Gründung der WTO als auch solche die danach zur Anwendung kamen und kommt zum Schluss, dass sie angesichts des grundlegend geänderten globalen rechtlichen Umfelds nicht mehr tragbar sind. Die Autorin empfiehlt daher, dass die auf NME Behandlung bezogenen Regeln und Praktiken vollständig aufgegeben werden und im Rahmen der gegenwärtigen Bemühungen um eine Modernisierung des gesamten WTO Regelwerks durch angemessene andere Regeln ersetzt werden sollten.
https://phaidra.univie.ac.at/detail/o:1354372
Keywords: Antidumpingrecht; Nichtmarktwirtschaftlichen Behandlung; Non-market economy

Sustainable tourism development in transfrontier conservation areas : a legal perspective - Mugadza, Amanda Tapiwa (North-West University, 2019)
Transfrontier conservation areas (TFCAs) originate from the idea of conservation across international boundaries. Within the SADC region, they are defined as areas or components of large ecological regions that straddle the boundaries of two or more countries, encompassing one or more protected areas, as well as multiple resource use areas. While the objectives of TFCAs are manifold, key among these are biodiversity conservation, improvement of livelihoods - poverty alleviation and economic development. Within SADC, tourism is identified as a key driver of these objectives. To explore this further, the study embarks on a case study of the Great Limpopo Transfrontier Conservation Area (GLTFCA), the oldest and second largest TFCA in the region, involving South Africa, Mozambique and Zimbabwe. From the GLTFCA, it is established that challenges exist with the manner in which tourism development is undertaken. However, it is further established that these challenges do not necessarily stem from the tourism development itself but from the weaknesses in the governance structures of this TFCA. In particular, the exclusion of local communities as key governance actors in the GLTFCA is seen to be detrimental to conservation and perpetuates poverty. Superimposed on these weaknesses, the tourism development therefore fails to adequately promote biodiversity conservation, improvement of livelihoods - poverty alleviation and economic development in the GLTFCA. To resolve these challenges, the study explores the concept of sustainable tourism development from a legal perspective guided by the question: what is the legal framework necessary, at domestic level – in TFCA participating countries to ensure that sustainable tourism development promotes the key SADC TFCA objectives? Through the aims or policy implications of sustainable tourism development, the study determines a legal framework comprising of the relevant TFCA governance actors as well as the governance-based tools that are necessary to promote the TFCA objectives. The domestic legal frameworks of the GLTFCA participating countries are measured against this legal framework to establish whether they promote sustainable toruism development. It is established that the domestic legal frameworks of South Africa, Mozambique and Zimbabwe, individually and as a whole, neither provide effectively for all relevant TFCA governance actors, especially local communities; nor for the tools that promote biodiversity conservation, the improvement of livelihoods-alleviation of poverty and economic development in the GLTFCA. Thus, the legal framework of the GLTFCA does not provide for sustainable tourism development as it should. For this reason, the study’s principal recommendation is the adoption, by all SADC TFCA participating countries, of a domestic legal framework for sustainable tourism development with specific elements which provides for the key TFCA governance actors as well as the relevant governance-based tools.
Keywords: Biodiversity conservation; Domestic legal framework; Economic Development; GLTFCA; Governance actors; Governance-based tools; Improvement of livelihoods; Sustainable tourism development; TFCAs; Tourism

Ticari işletme kavramı ve korunması - Üstündağ, Mustafa Emi̇r (Hasan Kalyoncu Üniversitesi, 2019)
"Bu tez çalışması ile işletme yöneticilerinin ticari belge tanzim ve hukuki süreçlerine ilişkin bilgi ve algı düzeyleri ortaya konmaya çalışılmıştır. İşletme yöneticileri içinde faaliyet gösterdikleri ülkenin hukuki kurallarına göre iş piyasası ve iş hayatında faaliyet gösterirler. Ve bu kurallar ticari hayat içinde onlar için en önemli bağlayıcı normlardır. Bu çalışma ilgi ticaret hukukunun iş hayatında en önemli faaliyet ve uygulama alanı bulan ticari belge tanzimi ve hukuki süreçlerinin yöneticiler tarafından ne seviyede algılandığının ortaya konması amaçlanmıştır. Tez çalışma dört bölümden oluşturulmuştur. İlk bölümümüz giriş bölümüdür. İkinci bölümde yönetim konuları, ticari belgeye ilişkin hukuki argümanlara yer verilmiştir. Üçüncü bölüm uygulama bölümüdür. Dördüncü bölümde ise sonuç ve yorumlara yer verilmiştir. With this thesis, the level of knowledge and perception of business executives regarding the issuance and legal processes of commercial documents has been tried to be revealed. Business executives operate in the labor market and business life according to the legal rules of the country in which they operate. And these rules are the most important binding norms for them in commercial life. With this study, it is aimed to reveal the level of perception of commercial document arrangement and legal processes, which find the most important field of activity and application in business life, by managers. The study is composed of four parts. Our first part is the introduction. In the second part, administrative issues and legal arguments related to the commercial document are included. The third part is the implementation part. In the fourth section, results and comments are given."
Keywords: Bilgi düzeyi; Business management; Commercial documents; Commercial law; Level of knowledge; Managers; Ticaret hukuku; Ticari belgeler; Yöneticiler; İşletme yönetimi

حماية الغير في العقود - خليل, إيمان (Ibn Khaldun University of Tiaret, 2019)
بانعقاد العقد صحيحا وبتوافر كل اركانه يرتب التزامات على المتعاقدين اذا كان العقد ملزما للطرفين وهذا ما يميز العقد الملزم لجانبين كعقد البيع مثلا فالبائع فيه يلتزم بتسليم الش ئ المبيع حسب الاتفاق الحاصل. هذه النتيجة هي منطقية يعكسها مبدأ نسبية اثر العقد التي نجدها في نص المادتين 230 و 220 من القانون المدني الجزائري، لكن هل صحيح ان هذا العقد لا يمس الغير الاجنبي كما جاء في نص المادة 230 او انه يمسه في شقه الموجب فقط؟ أي يكسبه حقا دون ان يلتزم بالشق السلبي للعقد كما نصت عليه المادة 220 من القانون المدني الجزائري. -وبالرجوع لقواعد القانون المدني ،نجد ان الغير لا يستطيع تجاهل وجود العقد، فالعقد بالنسبة للغير هو واقعة مادية أي قد يتاثر لها ايجابا او سلبا وهذا يعد خروجا عن النص المادة المذكورة اعلاه. عندما نذكر مصطلح نسبية اثر العقد فإننا نقصد نسبية الاشخاص وليس الموضوع ، سنقوم بتبيان مفهوم الغير ومفهوم النسبية وعندما نذكر النسبية منطقيا يجب ذكر اطراف العقد كلها من متعاقدين الذين بدورهما ينقسمان الى اصليين ونواب ومن خلف عام وخلف خاص ، ونذكر وايضا النسبية بالنسبة للغير ،بحيث نجد ان في كل من الفئات يوجد تداخل ففي بعض الحالات يصبح الطرف غير ويصبح الغير طرفا.حيث حاول المشرع أن يعطي للغير حماية قانونية كافية و ناجحة ،لاعتبارها كانت مؤطرة و متعددة الميادين و ذلك للمحافظة على المراكز القانونية التي وضع فيها الغير، واكتسبها بمناسبة العقد ،وذلك باضفاء وسائل تحميه و تدعم موقفه في العقد ،حتى و لو لم يكن طرفا فيه. تبينت أنها حماية متنوعة ،كقاعدة الاحتجاج و امكانية ابطال العقد أو تنفيذه من طرف الغير نفسه ،كل تلك القواعد اظهرت مدى تطور مكانة الغير، حيث نجد أن المشرع محاولة منه بوضع توازي بي حماية حقوق الطراف و حقوق الغير، مع تركيزه على الجانب الانساني ومن هو الطرف الضعيف الحسن النية في المنازعات ،لضمان عدالة الحماية ذلك أن العقد يجب أن يك ون وسيلة منفعة لأطرافه و أن تعم الكل ،منهم الغير.
Keywords: Contracts; Contrat; Groupe contractuel; Nullité; Partie; Protection juridique; Responsabilité contractuelle

L'image fidèle dans les sociétés commerciales de la République Démocratique du Congo : Vérifications empiriques au regard du système comptable OHADA - Halimana Hangi, Bernard (Université Protestante au Congo, 2018)
Le mobile de notre recherche est d’analyser les facteurs ou pesanteurs qui ont empêché les dirigeants sociaux et les professionnels du chiffre (directeurs administratifs et financiers, chefs comptables et comptables, auditeurs et contrôleurs de gestion, experts comptables et commissaires aux comptes)à produire, voire à certifier des états financiers de synthèse qui reflètent l’image fidèle des sociétés commerciales de la RD Congo. L’étude s’est effectuée au cours de deux premières années de mise en application du Système comptable de l’OHADA (SYSCOHADA), soit 2014 pour les comptes personnels et 2015 pour les comptes consolidés et les comptes combinés. Nous avons fait un tour rétrospectif sur l’exercice social 2013 ainsi qu’un regard projectif sur l’exercice 2016, dans le cadre de vérifications empiriques à ce sujet. En grosso modo, nos analyses se sont appuyées sur les données comptables et fiscales de 4 exercices sociaux (2013 à 2016). La toile de fond de notre étude était de savoir pourquoi les états financiers n’ont pas donné l’image fidèle du patrimoine, du résultat et de la situation financière. Cette notion d’image fidèle est consacrée par les articles 2 à 11 de l’Acte uniforme portant organisation et harmonisation des comptabilités des entreprises (AUOHCE), tel que révisé par l’Acte uniforme relatif au droit comptable et à l’information financière (AUDCIF) du 26 janvier 2017 ainsi que les articles 137 à 141 de l’Acte uniforme relatif aux Sociétés commerciales et au Groupement d’intérêt économique (AUSCGIÉ) ; à condition que les états financiers soient établis et présentés conformément aux dispositions des articles 25 à 34 de l’AUDCIF susvisé. Notre analyse est partie des vérifications empiriques sur les informations financières et fiscales de 173 sociétés commerciales et des réponses de 357 dirigeants sociaux des sociétés commerciales et des professionnels du chiffre qui ont répondu à notre questionnaire d’enquête. Les résultats de cette enquête, tout comme ceux des vérifications empiriques ont été recoupés et confirmés à partir de l’entretien semi-directif avec 38 informants qui ont vécu la transition du Plan Comptable Général Congolais (PCGC) vers le SYSCOHADA. De nos analyses, il a été démontré que les états financiers et d’autres documents comptables et de gestion courante des sociétés commerciales de la RD Congo n’ont pas reflété l’image fidèle des patrimoines, des résultats et des situations financières. Pour cause, il a été révélé que les dirigeants sociaux ainsi que les professionnels du chiffre ont établi et/ou certifié des informations financières influencées par des facteurs et pesanteurs politico-contractuels, conventionnels et socio-institutionnels. Ainsi, nous avons suggéré, qu’au-delà du formalisme mettant en relation les éléments de principaux états financiers (Bilan, Compte de résultat et Tableau des flux de trésorerie), il faille instaurer des mécanismes de durcissement de la réglementation comptable par un contrôle du niveau d’application du SYSCOHADA. Ce contrôle doit partir de l’examen des postes du Bilan à celui des soldes intermédiaires de gestion du Compte de résultat pour arriver à tirer les conséquences de la vérification de la comptabilité produite par les gestionnaires (dirigeants sociaux) et/ou certifiée par les professionnels du chiffre (consultants, auditeurs et commissaires aux comptes). Tous ces acteurs devront être invités au respect du Code d’éthique et de la Clause de conscience.
Keywords: AUDCIF; AUOHCE; AUSCGIE; Plan Comptable Général; SYSCOHADA

L'harmonisation du droit pharmaceutique en Afrique de l’Ouest : le cas de l’UEMOA - Palgo, Diane Horélie (Bourgogne Franche-Comté, 2018)
La protection de la santé par l’instauration d’une sécurité sanitaire dépend largement d’une organisation du marché pharmaceutique et de l’instauration d’un marché pharmaceutique commun. En Afrique de l’Ouest, particulièrement au sein de l’UEMOA, l’absence d’un tel marché facilite l’essor du marché illicite du médicament et empêche une libre circulation des produits de santé entre les États membres. Pourtant, le développement économique implique un système de santé efficace et sécurisé. Progressivement, émerge une prise de conscience des États membres de l’UEMOA de la nécessité de conjuguer leurs efforts pour une meilleure protection de la santé ; l’intégration juridique ainsi recherchée pouvant se réaliser au travers de plusieurs moyens : l’harmonisation, l’unification et l’uniformisation. L’harmonisation est le moyen d’intégration juridique que l’UEMOA a choisi pour mettre en place des normes plus efficaces et plus élaborées. Le rapprochement par harmonisation des réglementations pharmaceutiques devient ainsi un objectif primordial, en vue de l’instauration d’une sécurité sanitaire dans la zone communautaire. Pourtant, cette harmonisation, pour atteindre son objectif d’amélioration des systèmes pharmaceutiques, suppose un cadre juridique élaboré. Un processus d’harmonisation est alors mis en place et concrétisé par l’adoption de plusieurs instruments juridiques communautaires : directives, règlements et décisions. Cependant, l’UEMOA n’est pas la seule organisation sous-régionale qui vise pour objectif l’harmonisation du droit pharmaceutique dans la zone. D’autres organisations régionales et sous-régionales telles que la CEDEAO et l’UA, dont sont membres les États de l’UEMOA, visent également un rapprochement par harmonisation du domaine pharmaceutique. S’ajoutent alors aux difficultés de fonctionnement, au niveau interne et communautaire, des obstacles externes liés à l’appartenance des États de l’UEMOA à ces deux organisations. Ces obstacles vont compromettre l’efficacité du processus d’harmonisation. Il s’ensuit alors une nécessité de revoir le choix de l’instrument juridique de rapprochement, quitte à s’aventurer vers un rapprochement mixte des réglementations pharmaceutiques par une combinaison de deux moyens d’intégration juridique : l’harmonisation et l’unification. Health protection, the setting up of health security highly depend on an organization of the pharmaceutical market by the establishment of a common pharmaceutical market. In West Africa, particularly within WAEMU, the absence of such of market eases the rise in illicit drug market and impedes a free movement of health products between States. Yet, economic development involves an effective and secured health system. WAEMU’s member States awareness is emerging gradually, hence the necessity to join forces for better health protection ; therefore the long-awaited legal integration can be done through several means ; harmonization, unification, standardization. Harmonization is the means of legal integration that WAEMU has chosen to set up more effective and elaborate standards. Reconciliation through the harmonization of pharmaceutical regulations therefore becomes a key objective, with a view to setting up health security within the community zone. Yet, this harmonization, to achieve its objective of improving pharmaceutical systems, implies an elaborate legal framework. A process of harmonization is therefore set up and materialized by the adoption of several community legal instruments : guidances ; regulations, decisions. However, it should be noted that WAEMU is not the only sub-regional organization that has objective the pharmaceutical right harmonization. Other regional and sub-regional organizations such as ECOWAS, AU, of which WAEMU States are member, target also a reconciliation by the harmonization of the pharmaceutical area. In addition to the operating difficulties, at internal and community level, there are some external impediments related to the belonging of WAEMU States to those both organizations. Those obstacles will jeopardize the effectiveness of the harmonization process. Consequently, it is necessary to reconsider the choice of reconciliation legal instruments, even if that means venturing into a mixed reconciliation of pharmaceutical regulations through a combination of two means of legal integrations : harmonization and unification.
Keywords: Afrique occidentale; Droit pharmaceutique; Harmonisation; Harmonization; Health security; Intégration juridique; Legal integration; Lois uniformes (gouvernement fédéral); Pharmaceutical right; Pharmacie; Risques pour la santé; Services de santé; Sécurité sanitaire; UEMOA; Unification; Unification internationale; Union économique et monétaire Ouest africaine; WAEMU

Le statut de l'entreprenant dans l'espace OHADA - Ly, Ousmane Aliou (Université Cheikh Anta Diop, 2018)
Keywords: Droit OHADA; Entreprenant; Espace OHADA

La performance en droit des affaires - Pepino, Camille (Aix-Marseille Université, 2018)
Les opérateurs économiques sont confrontés à un fort accroissement de la concurrence combiné à des préoccupations sociales et environnementales désormais devenues indispensables. De ce constat, il semble que la performance qu’elle soit de type économique, social ou environnemental, soit devenue une valeur intrinsèque qui s’intègre ponctuellement à des obligations, ou engendre des obligations. Elle sera parfois extérieure au contrat et imposée par le droit lui-même. En ce sens, le législateur impose que la rémunération de certains dirigeants de sociétés soit obligatoirement indexée sur des critères de performances. Mais la performance sera parfois interne au contrat et constituera un élément essentiel pour ce dernier. Ces manifestations traduisent un mouvement d’ensemble rendant nécessaire la construction d’une réflexion juridique sur la performance, prisme de lecture devenu inévitable et particulièrement crucial. En dépit de l’attrait de la quête de performance, le droit est à la recherche d’un point d’équilibre de nature à permettre un développement économique dans les meilleures conditions, adossé au respect de l’environnement, naturel, humain, voire sociétal. C’est dans cette perspective que la dynamique de cette étude est construite. Elle appréhende la performance comme le fait d’atteindre un objectif, avec des moyens et des méthodes efficientes, tout en limitant les pertes financières et les effets néfastes. La performance est la nouvelle clé de lecture de la vie en société, et le droit des affaires s’impose à cet égard comme l’un des premiers relais
Keywords: Business law; Droit des affaires; Economic performance; Entreprises; Entreprises – Société; Environmental performance; Environnement; Performance environnementale; Performance sociale; Performance économique; Rentabilité; Social performance

La gestion du risque de contrepartie en matière des dérivés de gré à gré : approche juridique - Brouillou, Guerric (Université Paris 1, 2018)
Au lendemain de la crise financière de 2008, les autorités se sont emparées de la question du risque de contrepartie associé aux produits dérivés de gré à gré. Les dix années qui se sont écoulées depuis permettent de dresser le bilan de l’efficacité du cadre règlementaire alors mis en place. Cette étude s’attache à cartographier les différents éléments qui composent ou alimentent le risque de contrepartie en matière de dérivés de gré à gré et analyse l’efficacité des diverses techniques déployées pour le gérer. Les outils de gestion utilisés en matière de dérivés de gré à gré afin d’atténuer le risque de contrepartie reposent sur une pluralité de mécanismes juridiques (légaux ou contractuels). Si certains sont à la libre disposition des parties, d’autres leur sont imposés par la règlementation. Tous ces instruments participent – seuls ou conjointement – à atténuer réellement le risque de contrepartie. Mais chacun d’eux ne traite néanmoins qu’un aspect particulier de ce risque et aucun ne permet de l’annihiler totalement. Certaines situations viennent même parfois perturber l’efficacité des outils de gestion du risque de contrepartie et anéantissent leurs effets bénéfiques. On comprend in fine que la gestion efficace du risque de contrepartie suppose le respect de trois étapes : l’identification des risques attachés à chaque opération en présence doit précéder l’élaboration des outils de gestion en vue de leur atténuation, laquelle suppose enfin la prévention du risque d’inefficacité des outils utilisés. Dans tous les cas, la gestion du risque de contrepartie en matière de dérivés de gré à gré s’avère non seulement imparfaite mais aussi éminemment fragile.
Issue: 2018PA01D056
Keywords: Compensation centrale; Contrats; Contrats financiers; Counterparty risk management tools; Droit des affaires; Droit privé; Dérivés; Finances; Garanties financières; Instruments financiers à terme; OTC derivatives; Risque de contrepartie; Risque systématique; Résilitation-compensation

Indemnisation du préjudice économique en cas d'inexécution contractuelle : étude comparative en common law américaine, droit civil français et droit commercial international : application aux avant-contrats, atteintes à la réputation commerciale et activités sans base établie - Giaoui, Franck S. (Université Paris 1, 2018)
Force est de constater l'absence dans les textes de loi d'une définition précise de la réparation intégrale et a fortiori de règles d'évaluation des dommages-intérêts compensatoires. La doctrine tente bien de pallier ce vide en décrivant les différents types d'indemnisation, notamment aux États-Unis. Pourtant, la difficulté reste entière lorsque le préjudice existe mais que son estimation est délicate ou incertaine. En effet, ces questions sont considérées uniquement comme des questions de faits ; les juges du fond restent donc souverains, ce qui débouche sur une grande imprévisibilité pour les parties. Réduire l'imprévisibilité judiciaire du dommage passe par le choix et la définition d'un cadre de travail commun. S'appuyant notamment sur les résultats d'une analyse empirique comparative de centaines de cas de jurisprudence, l'étude formalise des prescriptions à l'intention des parties qui souhaitent améliorer leurs chances de succès dans le recouvrement des gains manqués et de la perte de chance. Elle évoque aussi la nécessité d'améliorer la pratique judiciaire dans l'application du droit actuel à la réparation intégrale. Surtout, elle aboutit à une conclusion normative fondamentale qui consisterait à considérer le préjudice économique et financier, les dommages intérêts et le calcul du quantum également comme des questions de droit. Dès lors, il relèverait d'une bonne justice que la Cour de cassation préconisa et contrôla l'usage de telle ou telle méthode d'évaluation. Chaque chef de préjudice économique serait ainsi qualifié juridiquement et la notion de réparation intégrale serait élargie pour indemniser plus complètement le préjudice économique difficilement quantifiable.Il ressort enfin que des barèmes référencés d'indemnisation peuvent être construits à partir de l'observation de précédents jugés d'inexécutions contractuelles. L'introduction de ces barèmes pourrait bénéficier aux chercheurs dans leurs débats académiques, aux parties dans la rédaction de leurs contrats, aux conseils dans leurs échanges précontentieux voire aux juges comme outil d'aide à la décision. Si ces barèmes étaient validés et partagés, ils pourraient donner naissance à des modèles d'intelligence artificielle de type machine learning dont la valeur -notamment prédictive -serait sans commune mesure avec ce qu'on en perçoit aujourd'hui. Law statutes and codes lack of a precise definition of the « full compensation » principle, and a fortiori they Jack of rules for assessing compensatory damages. The legal doctrine tries to fil] in the blank by describing the different types of damages awarded, notably in the United States. Yet, the issue remains full when the Joss is certain but its valuation remains complex or uncertain. The assessment of the economic Joss and the calculation methodology for damages are considered to be only matters of facts: trial courts and judges thus retain a sovereign power, resulting in great uncertainty for the parties. Reducing judicial uncertainty requires the choice and creation of a common framework. Based on the results of an empirical law and economics analysis of several hundreds of precedent cases, the dissertation formulates simple and practical suggestions for parties looking to improve their chances of success in recouping lost profits and lost opportunities. It also evidences which improvements of the judicial systems are required in order to actually implement the current right to full compensation. More importantly the research reaches a fundamental nonnative conclusion: economic Joss, compensatory damages and hence, the calculation of the quantum granted should be considered, not as mere matters of facts but also as matters of law. Henceforth, it would be logical that the Cour de cassation ( or the highest court) advises and controls the use of calculation methodology. Each head of damages would thus be legally qualified and the principle of full compensation would be extended in order to better compensate the loss when evaluating its quantum is complex. It finally results that referenced compensatory scales can be practically developed from compiling relevant legal precedents. The introduction of such scales would benefit academics in their debates, parties in the drafting of their contracts and counsels in their pre-trial exchanges. Eventually, judges could use them as tools to assist their rulings. If those scales were to be adopted and shared, they would enable the creation of such artificial intelligence as machine learning which value - notably the predictive value - would far exceed what is perceived today.
Keywords: Activités nouvelles; Agreement to agree; Agreement to negotiate; Avant-contrats; Commercial reputation; Common law; Contract breach; Dommages-intérêts; Droit civil; Droit commercial (droit international); Economic loss; Expectation damages; Gains manqués; Inexécution contractuelle; Justice prédictive; New business; Predictive Justice; Prejudice économique; Préjudice économique pur; Réputation commerciale

La concession : éléments de renouveau d'une catégorie contractuelle - Trimua, Arthur Lilas (Université de Poitiers, 2018)
La concession, instrument contractuel de coopération économique public-privé, connaît un engouement mondial. La relation tripartite vertueuse qu'elle établit entre l'autorité concédante, l'opérateur économique et les investisseurs a largement contribué à l'adoption de ce mécanisme d'origine française par divers systèmes juridiques sous l'appellation générique de partenariat public-privé (PPP). D'origine jurisprudentielle et longtemps protégé des influences extérieures, le modèle concessif bénéficie, sous l'empire de l'ordonnance du 29 janvier 2016 et du décret du 1er février 2016 relatifs aux contrats de concession, d'une européanisation de ses critères et de son régime juridique. En cristallisant le risque d'exploitation dans sa fonction de critère de discrimination ultime de la summa divisio de la commande publique, le nouveau droit des concessions bouleverse la hiérarchie des critères classiques d'identification du modèle concessif français. Cette évolution substantielle des éléments d'identité de la concession s'est accompagnée du renouvellement de son régime juridique. Cet environnement juridique transformé invite à une relecture globale du modèle français de la concession à travers la novation de ses éléments constitutifs et de son régime juridique.
Keywords: Bien de reprise; Bien de retour; Bien propre; Concession de service public; Concession de travaux publics; Concessions (droit administratif); Concessions (droit européen); Délégation de service public; Délégations de service public; Mandatory return assets; Operational risk; Operator owned assets.; Optional repurchase assets; Organisme de droit public; PPP; Partenariat public-privé; Personnes publiques; Public body; Public service concession; Public service delegation; Public works concession; Risque d'exploitation; Risque financier

Infraestrutura, regulção e internet: a disciplina jurídica da neutralidade das redes - Pereira Júnior, Ademir Antonio (Universidade de São Paulo, 2018)
Este estudo examina a Internet como uma infraestrutura, ou seja, um recurso social de larga escala que produz benefícios a partir das atividades que ela permite sejam desenvolvidas. O gerenciamento das redes que compõem a Internet sem que haja discriminação de usuários e utilizações diversas (gerenciamento como commons) pode gerar benefícios sociais substantivos, apropriados pelas partes diretamente envolvidas ou na forma de externalidades positivas. O design original da Internet estabeleceu uma arquitetura de rede que inviabilizava que os provedores de Internet pudessem influir sobre a camada dos aplicativos (conteúdos e serviços), garantindo assim a prevalência de acesso amplo e não discriminatório às redes. Essa opção de design foi posteriormente associada à noção de neutralidade (cunhando a expressão neutralidade de rede) e foi responsável por viabilizar intensa dinâmica de inovação (que ocorria independente de permissão dos detentores das redes e de modo descentralizado) e expansão das capacidades dos indivíduos, que passam a produzir e acessar conteúdos sem restrições. Essa percepção sobre a relevância do gerenciamento não discriminatório da Internet deu origem ao debate sobre a necessidade de regulação ex ante para disciplinar a neutralidade das redes, que conta com extensa e confusa produção acadêmica. A partir do exame sistemático dessa literatura, o trabalho procura demonstrar que há incentivos para que os provedores de Internet passem a adotar condutas exclusionárias e exploratórias baseadas na diferenciação de conteúdos e serviços que trafegam por suas redes. Essas práticas podem subverter a dinâmica de inovação e criar óbices ao exercício de capacidades pelos indivíduos, alterando o balanço de externalidades positivas geradas à sociedade e benefícios aos usuários das redes, o que serve de justificativa para propostas de regulação com o fim de preservar as condições de gerenciamento não discriminatório. O trabalho segue então para uma análise dos benefícios que se procuram efetivar com a regulação e potenciais custos de sua implementação, procurando apresentar um quadro amplo, transparente e sistemático dos potenciais custos e benefícios das propostas de regulação. Esse exame é realizado com a consideração particular de cada regra usualmente apontada para integrar a regulação, num exercício de identificação e sopesamento dos custos e benefícios de cada uma delas. Esse exame revela que as regras que compõem as propostas de regulação de neutralidade de rede têm potencial de gerar benefícios relevantes e que tendem a compensar os custos a serem sopesados. Mesmo quando os potenciais custos da regulação sejam consideráveis e tornem mais complexo o sopesamento dos benefícios, os custos identificados poderiam ser mitigados com a adoção de modelos de negócios alternativos e que não ferem regulação. Dessa forma, a opção pela regulação parece ter um balanço positivo, permitindo a manutenção da Internet como uma infraestrutura capaz de gerar benefícios sociais substantivos.
Keywords: Cost-benefit analysis; Externalities; Innovation; Internet; Network neutrality; Regulamentação comercial; Regulation

La volonté débordée par la morale : l'exemple de la vente d'immeuble - Cauvin, Grégory (Université Paris-Est, 2018)
La vente immobilière est devenue un contrat de méfiance où s’entrechoquent différents droits et obligations. Ce sont les droits du vendeur contre ceux de l’acquéreur voire des tiers comme les occupants du bien. Face à cette crise de confiance, les enjeux moraux de ce contrat présentent un réel intérêt surtout au regard de la moralisation de la vente d’immeuble par l’action combinée du législateur et du juge. Ces derniers vont s’intéresser au bien des contractants dépassant ainsi le domaine strict du droit. En effet, la morale est évaluée selon des critères d’appréciation de bien ou de mal alors que la justice procède à son évaluation sur la base de critère de juste ou d’injuste. Le droit, objet de la justice, concerne « le juste rapport des biens et des choses réparties entre citoyens ». Le bien consistant « dans une juste mesure, un point d’équilibre où se réalise l’harmonie du tout et de ses parties », le domaine de l’étude concerne tout aussi bien l’équilibre du contrat de vente immobilière que la conduite des acteurs du contrat.
Keywords: Contrat; Immobilier; Morale; Obligations; Vente d'immeuble; Volonté

Modifying contract law principles to accommodate automated transactions in South Africa - Ramokanate, L. L. (North-West University, 2018)
Modern electronic commerce is chiefly characterised by the use of unattended computers in the negotiation and conclusion of agreements. Commonly referred to as "electronic agents," these computers assist their users to negotiate better and profitable deals in virtual marketplaces. In South Africa, the legal force and effect of automated transactions, i.e. agreements concluded by electronic agents, is addressed in section 20 of the Electronic Communications and Transactions Act 25 of 2002 (hereinafter referred to as the ECT Act). According to section 20 (a) of the ECT Act, a valid and enforceable agreement will be formed where an electronic agent performs an action required by law for agreement formation. The same statute provides further in section 20 (b) that a valid and enforceable agreement will be formed where all the parties to a transaction or either one of them uses an electronic agent. The overall effect of these provisions is that an agreement cannot be denied legal validity and enforceability on the ground that an electronic agent was used, whether by one or both parties, to conclude it. Likewise, an agreement cannot be denied legal validity and enforceability on the ground that no human being took part in its formation. Although the ECT Act provides as a general matter that automated transactions are valid and enforceable in South Africa, that statute does not, however, create new rules for the formation of such agreements. This is made clear in section 3, which provides, amongst others, that the ECT Act should not be interpreted to exclude the application of the common law of contract to electronic transactions. Therefore, as with traditional or non-automated agreements, automated transactions too must satisfy the individual requirements of a valid contract at common law. As a matter of fact, the common law theory of contract formation is predominantly based on the assumption that human volition will always play a pivotal role in the making, acceptance or rejection of offers. For that reason, this research proceeds on a strong hypothesis that common law rules and principles pertaining to the formation of agreements are either insufficient or inadequate to accommodate the validity of agreements concluded by computers without the immediate intervention of their users. Consequently, the aim of this research is to discuss how the rules and principles of the common law of contract can be modified or developed in order to accommodate, within the common law theory of contract formation, the statutory validity of automated transactions in South Africa. The discussion of this research is limited to five legal issues, namely the basis of contractual liability in automated transactions, the analysis of offer and acceptance in automated transactions, the time and place of contract formation in automated transactions, the incorporation of standard terms and conditions in automated transactions, and the treatment of mistakes and errors in automated transactions. These issues are discussed first with reference to South African law, primarily with the purpose of determining the extent to which relevant common law rules and principles provide adequate solutions to specific challenges posed by automated transactions. To the extent that relevant common law rules and principles do not provide adequate solutions to the challenges of automated transactions, recommendations are made in this research for their development or modification. As shall be demonstrated in the course of this work, in relation to some of the abovementioned legal issues, the development or modification of common law rules has been done by the ECT Act. These "statutory developments or modifications of the common law" are also discussed in this work, primarily with the aim of determining the extent to which they provide adequate solutions to specific challenges posed by automated transactions. To the extent that these statutory modifications of the common law do not provide adequate solutions to the challenges of automated transactions, recommendations are made in this work on how the relevant provisions of the ECT Act may be interpreted by courts of law or amended by Parliament in order to strengthen the response of that statute. The abovementioned legal issues are also discussed in this work with reference to US and UK law, primarily with the purpose of determining how the law addresses the challenges of automated transactions in these jurisdictions, and to draw valuable lessons for the development or modification of South African contract law.
Keywords: Automated transactions; Autonomous electronic agents; Contract formation; Contract law; Passive electronic agents

Acentenin ücret hakkı - Teki̇n, Ufuk (Ankara Üniversitesi, 2018)
Ücret hakkı acentenin en temel hakkı olup Türk Ticaret Kanunu'nun 113 ila 116. maddeleri arasında düzenlenmiştir. Hangi işlemlerin acenteye ücret hakkı kazandıracağı 113. maddede yer almaktadır. Bu hükme göre acente doğrudan kendi katkısıyla kurulan işlemler sebebiyle ücrete hak kazanabileceği gibi, müvekkile daha önce kazandırdığı müşterilerle sonradan kurulan aynı nitelikteki işlemler sebebiyle de ücrete hak kazanabileceği ifade edilmiştir. Söz konusu hükme göre ayrıca acente, kendisine belirli bir bölge veya müşteri çevresi bırakıldığı takdirde, bu bölgede veya müşteri çevresiyle kendi katkısı olmadan kurulan işlemler sebebiyle de ücrete hak kazanabilecektir. Yine aynı hükme göre acente, bazı şartların varlığı halinde acentelik sözleşmesinin bitiminden sonra kurulan işlemler sebebiyle de ücrete hak kazanmaktadır. Acentenin ücrete hak kazanabilmesi için Türk Ticaret Kanunu m. 113'e göre ücrete hak kazandıran bir işlemin varlığına ek olarak, m. 114'te ifade edildiği üzere kurulan işlemin ifası da gerekir. İşlemin ifasıyla doğan ücret hakkı, doğumu tarihinden itibaren en geç üç ay içinde ve her halde sözleşmenin sona erdiği tarihte muaccel olur (m. 116). Acentenin, ücret istemi, muacceliyeti ve hesaplanması bakımından önemli olan bütün konular hakkında kontrol hakkı bulunmaktadır. Bu hak, onun bilgi alma, müvekkilin defter kayıtlarının suretlerinin gönderilmesini talep ve inceleme hakkı olmak üzere üç haktan oluşmaktadır. Çalışmamızın birinci bölümünde Türk ve karşılaştırmalı hukukta konunun düzenlenişi ile kavramsal çerçeve üzerinde durulacak; ikinci bölümünde ücrete hak kazanılmasının şartları ele alındıktan sonra üçüncü bölümünde ücretin belirlenmesi, hesaplanması ile ödenmesi ve ücrete ilişkin kontrol hakkı açıklanmaya çalışılacaktır. The right of remuneration, which regulated between the Articles 113 to 116 of the Turkish Commercial Code, is the most fundamental right of commercial agent. According to Article 113, it is stated that the commercial agent has the right of remuneration due to the transactions established by its own contribution. Commercial agent has the right of remuneration also for same quality of transactions, which established later with the former customer. According to same Article, the commercial agent may also be entitled to remuneration, whether it is left in a certain area or customer environment, due to the transactions established in this area or the customer environment even without its own contribution. It is pointed in the same Article that, commercial agent also has the right of remuneration due to transactions established after the end of the commercial agency contract in the presence of certain conditions. As indicated in the Article 114, it is also necessary to perform the transaction, which gives the commercial agent the right of remuneration. The remuneration arising from the performance of the transaction shall be due within three months at the latest from the date of birth and in any circumstances at the date on which the contract is concluded (Article 116). The commercial agent has the right to control all matters that are important in terms of remuneration, accural and calculation. That right includes, the right to demand information, copies of the commercial book records of the client and examination. In the first part of our work we will focus on the regulations and conceptual framework of Turkish and comparative law. After considering the conditions of the acquisition of the remuneration in the second part, it is aimed to explain the determination and the calculation of the remuneration, payment and the control right of commercial agent about the right of remuneration in the final section.
Keywords: Acenteler; Agents; Commercial law; Ticaret hukuku; Turkish Commercial Code; Türk Ticaret Kanunu; Wage; Wage account; Wage fixing; Ücret; Ücret belirleme; Ücret hesaplama

Le contrat électronique International - Edderouassi, Meryem (Université Grenoble Alpes, 2017)
La réflexion sur la réglementation des contrats électroniques internationaux a pris, ces dernières années, une ampleur sans précédent.L’usage accru des communications électroniques à l’échelle internationale participe de manière remarquable à améliorer l’efficacité des activités économiques et sociales, à renforcer les relations entre Etats et à offrir de nouvelles possibilités de débouchés à des parties et à des marchés auparavant isolés.Pour cette raison, l’adoption de règles uniformes propres à éliminer les obstacles et valoriser les contrats électroniques internationaux serait susceptible de renforcer la certitude juridique et la prévisibilité commerciale des contrats internationaux et pourrait aider les États à avoir accès aux itinéraires commerciaux modernes.Le contrat électronique international constitue une nouvelle sphère qui mérite une recherche analytique afin de lui octroyer une sécurité juridique indispensable à son développement.Ce travail de recherche vise, donc, à élaborer une analyse systématique critique de la réglementation en vigueur qui régit le contrat électronique international et à examiner alors les textes existants aujourd’hui au regard des attentes de l’époque.Il vise à trouver les moyens juridiques susceptibles de garantir plus de sécurité au contrat électronique international.
Keywords: Commerce électronique; Contract; Contrat électronique; Contrat électronique international; Droit commercial (droit international); Electronic contract; International electronic contract; Sécurité juridique

L'immatriculation au registre du commerce : étude des droits tunisien et français - Ouali, Dorra (Université Paris 1, 2017)
Le registre du commerce présente le double aspect d'institution civile et d'institution de police. L'intérêt privé des tiers et l'intérêt public de l’État sont simultanément présents et protégés. Mais, on peut se demander si les rédacteurs de la loi relative au registre du commerce n'ont pas créé une situation délicate en ne tenant pas en compte suffisamment le souci de la sécurité juridique. La réponse à cette question est tributaire de l’étude des effets juridiques attachés à l'immatriculation. On envisage une étude comparative du droit tunisien et du droit français à travers laquelle on a pu constater qu'une définition de l'immatriculation par l'effet constitutif n'est pas apte à appréhender cette institution dans son ensemble. Il s’agit d’une notion ambivalente. Elle est ambivalente quant à son rôle à cause de l'hétérogénéité de son effet constitutif et de la diversité de ses effets. Elle est aussi ambivalente quant à sa finalité puisque le souci de la protection individuelle des tiers ne constitue pas son objectif prioritaire. D'abord, une certaine existence juridique est reconnue à la société avant son immatriculation. Il existe même une notion particulière de personnalité morale, dite à la fois judiciaire et processuelle, forgée par le juge civil pour les besoins du procès et en dehors de toute formalité d'immatriculation. Ensuite, le contrôle auquel est soumise l'immatriculation demeure un contrôle formel ; il n'empêche pas l'annulation de la société immatriculée. Enfin, l'immatriculation ne purge pas les irrégularités de la situation extériorisée aux tiers, elle crée désormais, une situation appareille. A travers la technique de la présomption et celle de l'opposabilité mises en œuvre par l'immatriculation, le législateur prend la défense de l'apparence sur la réalité. Il admet aussi la qualification de fait d'une situation non immatriculée. Cependant, les règles régissant l'immatriculation et le défaut d'immatriculation paraissent être insuffisantes. D'une part, elles ne peuvent régler tous les litiges, d'où l'intérêt du recours à la théorie d'apparence afin d'assurer aux tiers de bonne foi une sécurité absolue, D'autre part, la prise en considération de la situation de fait s'avère inutile puisqu'on a noté une assimilation quasi-complète entre le commerçant non immatriculé et celui immatriculé. Le contraste est saisissant avec la notion de société de fait puisque c'est le législateur qui accepte de l'assimiler à la société de droit. Pour faire face au risque de perturber l'ordre juridique engendré par cette assimilation, le législateur a favorisé la régularisation de la situation à travers l'injonction d'immatriculation et l'immatriculation d'office. Puisque ces mesures sont réservées aux seules personnes physiques, se pose alors avec acquitté la question de les généraliser pour intéresser même les sociétés non immatriculées. The register of commerce entails a dual aspect of both a civil institution and of an administrative police. The private interest of the third party as well as the public interest of the State are simultaneously present and safeguarded. Nevertheless, one might ask if the drafters of the law pertaining to the register of commerce have set up a critical situation by not taking into account sufficient concern for the legal security. The answer to this question depends on the study of the legal effects linked to registration. The target of this paper is to provide a comparative study of the Tunisian law and French law whereby it has been found that a definition of the registration by its constituent effect is not able to tackle this institution as a whole. It is about an ambivalent registration concept. It is ambivalent as to its role because of the heterogeneity of its constituent effects and the diversity of these effects. It is also ambivalent as to its purpose, since protecting the third party is not its priority. First, a certain legal existence is admitted to the company before its registration. There exists even a particular notion of the artificial entity of the company which is considered both procedural and legal, advocated by the judge in order to satisfy the needs of the case far away from the registration formalities. Moreover, the control that registration is subject to prove to be a very formal one i.e. it does not prevent the dissolution of the registered company. Finally, registration does not purify the anomalies of the situation that a third party may face as it creates as such an apparent situation. Through the presumption technique as well as the opposability implemented by registration, the legislator is much more defending the appearance than the reality. The legislator also acknowledges a qualification of a nonregistered situation. However, registration rules as well as its defects turn to be insufficient. On the one hand, it does not solve all lawsuits, which makes the theory of appearance the best guarantee of an absolute security for third parties. On the other hand, taking into account a de facto situation turns to be useless as we have noticed a quasi-complete assimilation between a registered trader and a non-registered one. The contrast is striking with the notion of the de facto situation since the legislator has accepted to treat it in the same way as a registered company. In order to avoid the disturbance of legal order caused by this simulation, the legislator opted for a peaceful settlement of the conflicting situation through either a judge or a court order for registration. Since these measures are the prerogatives of a physical person, the question to tackle is to what extent these measures can be extended to suit the interests of the non-registered companies.
Keywords: Apparence; Artificial entity; Commerce (réglementation); Commerçant; Effet constitutif; Immatriculation; Opposability; Opposabilité; Personne morale; Personnes morales; Registration; Régularisation; Situation de fait; Trader

Le règlement des litiges survenant des contrats de partenariats public-privé (PPP / PFI) : recherche d’une meilleure gestion des sources des litiges dans les contrats de PPP : enjeux et conséquences pour l’Egypte - Eissa Zakaria Abdelsalam, Nora (Université Lille 2, 2017)
Le partenariat public privé est un instrument pour la réalisation des objectifs du développement en Egypte. Sur le plan international, le recours aux PPP soulève des difficultés compliquées à résoudre. La nature complexe de ce type de projets augmentent la probabilité de litiges entre les parties. L’analyse comparée des expériences britannique et française, permet d’élaborer une référence pour le gouvernement égyptien en matières des réformes juridique et économique. Dans le cadre d’améliorer la gestion des projets de PPP en Egypte, deux approches peuvent être adressées dans notre recherche. En premier lieu, le développement d’une méthodologie de gestion efficace des risques par l’analyse de types des risques attachés aux PPP pendant le cycle de vie du projet. En deuxième lieu, la présentation des mécanismes les plus efficaces de résolution des litiges découlant des projets de PPP. Public-private partnership is an instrument for achieving development objectives in Egypt. On the international level, the use of the PPP model raises complicated challenges and difficulties. The complex nature of such projects increase the probability of disputes between the parties. The comparative analysis of the British and French experience allows the elaboration of a reference for the Egyptian government in the legal and economicreforms. In order to improve the management of PPP projects in Egypt, two approaches can be addressed in our research. First, the development of an effective risk management methodology through the analysis of the types of risk associated with PPP during the life cycle of the project. Second, the presentation of the most effective mechanisms for the resolution of disputes arising from PPP projects.
Keywords: Egypte; Gestion des risques; PFI; PPP; Partenariat public-privé; Pays en développement; Projets d’infrastructures; Étude comparative

Os usos comerciais: da formação dos tipos à interpretação e integração dos contratos empresariais - Comiran, Giovana Cunha (Universidade de São Paulo, 2017)
Habitualmente, o tema dos usos no Direito Comercial, é tratado com base na distinção funcional entre usos normativos e usos interpretativos. Aqui nos propomos a demonstrar que o recurso aos usos não só é necessário, mas está justificado na gênese dos tipos contratuais, especialmente nos contratos socialmente típicos, sendo sua aplicação sempre casuística. A chave para compreensão do objeto desta tese está em saber: (i) se os usos comerciais são aptos a gerar regras costumeiras; (ii) se é possível sustentar a existência de uma regra costumeira meramente dispositiva, ou se há supletividade, ou efetiva cogência; (iii) se os usos comerciais são apenas convencionais, ou se há usos comerciais com força prescritiva por si só, de forma autônoma, ou dependente da sua apreensão por negócio jurídico, remissão legal ou decisão judicial. Para tanto, depois de um breve assentamento das premissas teóricas adotadas (Capítulo I) tentaremos afastar a polissemia que fere o termo usos, descrevendo os múltiplos significados e as diferentes dimensões dos usos (Capítulo II). Posteriormente, passaremos a investigar o papel dos usos, primeiramente como formadores de tipos contratuais (Capítulo III), e, em seguida, na interpretação e integração dos contratos mercantis (Capítulo IV). Cremos ter comprovada a hipótese inicial. O papel dos usos nos contratos empresariais justifica-se pela conjugação entre a autonomia privada e a tutela das expectativas das partes pela confiança. Todavia, a aplicação dos usos aos contratos mercantis será sempre casuística. Parece-nos, assim, que é possível traçar alguns parâmetros, com base na experiência, oferecendo instrumental mais eficiente à tomada de decisão mais adequada por aqueles que aplicarão o Direito, minimizando, destarte, a assistematicidade e a insegurança jurídica inerentes ao casuísmo. Nosso objetivo estará alcançado se conseguirmos oferecer alguns critérios que permitam maior racionalidade e sistematicidade no emprego dos usos.
Keywords: Commercial uses; Contract type; Contracts; Contratos; Interpretation; Interpretação e integração; Princípio da confiança; Tipo contratual; Trust; Usos comerciais

Du Registre du Commerce et des Sociétés vers un registre de l'entreprise ? Réflexions sur une évolution jugée nécessaire - Weizman, Yoni (Université Paris 9 Dauphine, 2017)
Fondé en 1919, le Registre du Commerce et des Sociétés, tenu par le greffe de chaque tribunal de commerce, a largement évolué depuis pour s'adapter à la vie des affaires, aux évolutions juridiques de son environnement et aux attentes des entreprises assujetties. Institution centrale en matière économique, le Registre du Commerce et des Sociétés peut paraître efficace et simple d'accès. Pourtant, de nombreuses évolutions semblent naturellement devoir s'imposer au régime du Registre du Commerce et des Sociétés et des registres ou répertoires similaires, afin de simplification des démarches d'entreprises, de centralisation des données et d'efficacité de la publicité. Les instances européennes imposent aux Etats membres de nouvelles obligations en matière de registres commerciaux. Il semble indispensable de réformer le Registre du Commerce et des Sociétés, ensuite de quoi il serait opportun de proposer l'institution d'un registre de l'entreprise, pour intégrer les exigences européennes et pallier les inconvénients des différents régimes actuels.
Keywords: Business register; Centralisation; Centralization; Clerk of business tribunal; Droit commercial; Dématérialisation; Entreprise; European authorities; Firm register; Greffe du tribunal de commerce; Legal advertising; Publicité; Registre du commerce; Registre du commerce et des sociétés; Tribunaux de commerce

La prévisibilité en droit des contrats - Marignol, Ludovic (Université Toulouse 1 Capitole, 2017)
La prévisibilité est une notion omniprésente en droit des contrats. La loi et la jurisprudence y font parfois référence de manière explicite (prévisibilité du dommage, imprévisibilité du cas de force majeure), mais elle est plus souvent mise en œuvre par le biais de mécanismes qui lui servent, en quelque sorte, de « prête-noms » (devoir de loyauté, principe de sécurité juridique, contrôle des clauses abusives, etc…). Pourtant, la nature même du mécanisme contractuel, que l’on définit souvent comme un acte de prévision, incline à penser que la prévisibilité a vocation à jouer un rôle bien plus important que celui qui lui est actuellement reconnu dans le droit positif. La réforme du droit des contrats par l’ordonnance n°2016-131 du 10 février 2016 a d’ailleurs fortement accentué ce rôle, en conférant à la notion une fonction réellement normative des comportements contractuels (introduction des actions interrogatoires, consécration d’un devoir général d’information, encadrement des négociations sous l’égide du principe de bonne foi, etc.). L’étude de ces diverses manifestations et de l’évolution d’ensemble du droit positif au cours des dernières décennies, sous l’influence du droit de l’Union européenne et des instruments d’harmonisation internationale du droit des contrats, conduit donc à s’interroger sur le caractère opportun d’une élévation de la notion au rang de principe directeur à part entière de la matière. Cela permettrait de proposer un nouvel équilibre entre les rôles respectifs du droit positif et de la convention dans le rapport au risque, et une responsabilisation accrue des contractants dans la gestion de celui-ci.
Keywords: Contrats; Imprévision (droit); Prévisibilité; Prévisibilité juridique; Risque (droit); Sécurité juridique

Le mandataire judiciaire dans l'espace OHADA - Djerma, Ousmane Bazoumana (Université Cheikh Anta Diop, 2017)
Keywords: Espace OHADA; Mandataire judiciaire

Aspectos jurídico-mercantiles de la suscripción de Servicios de computación en la nube por pequeños empresarios; en particular, implicaciones en el sector turístico - Rosselló Rubert, Francisca Maria (Universitat de les Illes Balears, 2017)
[cat]Aquesta tesi doctoral es centra en la contractació de serveis de computació al núvol en la modalitat d'implementació pública per part del petit empresari, que té lloc en línea i a través de condicions generals. La modalitat de núvol públic permet al petit empresari una implementació económica i senzilla de recursos de computació que es reben mitjançant Internet, on el proveïdor s'encarrega de l'adquisició, manteniment i actualització dels sistemes informàtics que sustenten el servei. El nostre treball pretén donar un tractament uniforme als continguts més habituals dels contractes cloud no negociats, i especialment, a les obligacions que integren la relació jurídica entre petit empresari suscriptor i proveïdor dels serveis. D'altra banda, es vol determinar la naturalesa jurídica que es correspongui amb la generalitat dels contractes de núvol públic. Per finalitzar, es proposen solucions a la problemàtica específica derivada d'aquests nous i habituals contractes, relacionades amb la titularitat de les dades migrades, la protecció de la privacitat i el destí de les dades remanents als sistemes del proveïdor quan el contracte s'hagi extingit. Pel que fa als contractes cloud que suscriu el petit empresari del sector turístic, volem recollir els serveis d'implementació de núvol públic més populars, i identificar-ne els aspectes que resulten especialment problemàtics, com la continuitat del servei i els factors de disponibilitat o les repercusions a la reputació de l'establiment o servei turístic.
URI: https://www.tdx.cat/handle/10803/563079
Keywords: Cláusules abusives; Computació al núvol; Contractació turística; Contractes d'adhesió; Contractes de serveis de Cloud Computing; Dret Mercantil; Obligacions contractuals; Petit i mitjà empresari; Propietat intellectual; Protecció de dades; Responsabilitat contractual

Redes contratuais com função de distribuição - Drews, Rafael Induzzi (Universidade de São Paulo, 2017)
A presente tese versa sobre redes contratuais com função de distribuição, assim entendidas aquelas formadas por contratos de distribuição, concessão comercial - regidos pela Lei 6.729/79 - e franquia. Nessas redes, o organizador ou líder (fornecedor, fabricante ou franqueador) mantém contratos bilaterais homogêneos com cada um dos distribuidores, concessionários e franqueados, os quais, por sua vez, não mantêm relação contratual formal entre si. Ao líder são reservadas diversas prerrogativas contratuais que lhe possibilitem organizar e controlar o funcionamento da rede, com vistas a uma maior eficiência global e ao fortalecimento da marca. O trabalho procura definir essas redes e compreender como o direito, em especial o direito contratual, deve tratá-las. Sustenta-se que elas não se esgotam nos contratos bilaterais que as formam, sendo dotadas de uma dimensão coletiva que, embora não se amolde às categorias tradicionais do direito privado, é relevante para o direito contratual. Apresenta-se contribuição à identificação de vetores para o tratamento jurídico das redes.
Keywords: Commercial concession; Concessão comercial; Contractual networks; Contratos; Direito Comercial; Distribution; Franchise; Franquia; Interest of the network

طرق تحديد القانون الواجب التطبيق على عقود التجارة الدولية - عيد, عبد الحفيظ (جامعة مولود معمري, 2017)
تظهر طرق تحديد القانون واجب التطبيق على عقود التجارة الدولية في كل من المنهج التنازعي الذي يقوم على قاعدة إسناد و المنهج المباشر الذي يقدم الحل للنزاع بطريقة مباشرة وذلك بتطبيق قواعد قانونية تهتم بتنظيم العلاقات التجارية ذات البعد الدولي والتي تعرف بقواعد التجارة الدولية . يعتبر المنهج التنازعي من أقدم مناهج التي عرفتها نظرية التنازع والتي عرفت تطورات تعكس الفكر الفلسفي والاقتصادي والقانوني الذي يتخلل كل مرحلة من هذا التطور إلى أن إستقر في الأخير مبدأ سلطان الإرادة على ضوؤه يتم تحديد قانون العقد الدولي . مع تطورات الحاصلة في التجارة الدولية خاصة بعد التطور العلمي والتكنلوجي وتطور وسائل النقل وظهور مجتمع خاص يمارس هذه التجارة، ظهرت الحاجة إلى تطبيق قواعد قانونية ذات مضمون عالمي تستوعب تعقيدات هذه العقود التي تجاوزت المفاهيم الكلاسيكية التي جاءت بها القوانين الداخلية التي صدرت لتنظيم العقود الداخلية . Les modes de détermination de la loi applicable aux contrats de commerce international Les modes de choix de la loi applicable sur les contrats de commerce international se dégagent à la fois de l’application de la méthode dite conflictuelle qui se base sur la règle du rattachement, et de la méthode dite directe qui propose une solution directe au litige et ce, en application des règles régissant les relations à caractère international. La méthode dite conflictuelle est la plus ancienne ; elle a connu plusieurs étapes dans son évolution qui ont caractérisées la pensée philosophique, économique et juridique, jusqu’à l’émergence du principe de l’autonomie de la volonté sur lequel se base le choix de la loi applicable sur le contrat international. L’évolution connue dans le commerce international notamment au plan scientifique et technologique, l’évolution des moyens de transport et l’apparition d’une société qui pratique ce commerce, a fait apparaitre le besoin de règles à vocation mondiale prenant en compte la complexité de ce type de contrats qui dépassent largement les concepts classiques liés aux contrats internes.
Keywords: Arbitrage commercial international; Contrats commerciaux internationaux; Loi applicable; Pouvoir de volonté; Règles d'attribution; التحكيم التجاري الدولي; القانون الواجب التطبيق; سلطان الإرادة; عقود التجارة الدولية; قواعد الإسناد

The impact of climate change law on the principle of state sovereignty over natural resources - Van Wyk, Sanita (Stellenbosch University, 2017)
This dissertation serves to expand the means within international law by which to address the global interdisciplinary crisis that is climate change. The principle of sovereignty over natural resources is identified as a principle of international law, evolutionary in nature, fundamentally connected to the international legal climate change regime, and able to be impacted by the effects of climate change. The gravity of climate change is illustrated, as is the intricacy and composition of the international legal climate change regime. In the process, a particular shortcoming of the international legal climate change regime is identified, namely the lack of state compliance with climate commitments made in terms of the Kyoto Protocol 1997 and the Paris Agreement 2015. The gravity of the effects of climate change warrants the repositioning of any principle of international law that is able to address this shortcoming of the international legal climate change regime and increase the effectiveness of the regime. In this regard it is determined, more specifically, that the gravity of the effects of climate change warrants a reinterpretation and reconfiguration of the principle of sovereignty over natural resources. Climate change, forming part of the general, growing, global concern for environmental conservation and sustainable development, influences the interpretation and configuration of state rights and state duties in terms of the principle by eliciting an interpretation that restricts state rights and expands state duties. Furthermore, the gravity of the effects of climate change on the well-being of people, warrants a reinterpretation and reconfiguration of the principle of sovereignty over natural resources as a people-oriented principle as opposed to the conventional state-oriented principle, and ought to be applied with due regard to the rights of people in terms of the principle. The right of people in terms of the principle of sovereignty over natural resources, is identified as the right to economic selfdetermination, which gives effect to the right of people to dispose freely of natural resources. Should this right be promoted in future applications of the principle of sovereignty over natural resources, the right may well be established as constituting a significant basis on which people are able to hold states accountable for climate commitments made in terms of the Kyoto Protocol 1997 and the Paris Agreement 2015. In this way, the principle of sovereignty over natural resources, specifically the implementation of the right of people to dispose freely of natural resources in terms of the principle, presents a negative incentive for state compliance with climate commitments and can contribute to addressing the lack of state compliance within the international legal climate change regime. In summary, this dissertation proposes that the grave effects of climate change warrant a repositioning of the principle of sovereignty over natural resources that allows it to constitute a contribution to climate change law and the global fight against climate change.
URI: http://hdl.handle.net/10019.1/101171
Keywords: Climatic changes; Convention on Climate Change 1997; Convention on Climate Change 2015; Environmental law; Kyoto Protocol; Natural resources; Paris Agreement 2015; Self-determination; Sovereignty; United Nations Framework

La fiscalité des groupes de sociétés : étude comparée - Boumeddane, Zaza (Université d'Oran 2 Mohamed Ben Ahmed, 2017)
La fiscalité des groupes de sociétés intéresse le monde des affaires et tout contribuable. Le régime fiscal des sociétés est très incitatif à la création de groupes. Cela dit, c’est un régime fiscal récent en Algérie, son application nécessite des conditions. Il peut faire l’objet d’une révision. Le code fiscal algérien s’est ressourcé beaucoup du Code General des Impôts français. La détermination du résultat fiscal d’ensemble est restée une très grande problématique. Le résultat fiscal nécessite différents retraitements. Les transferts de bénéfices et le régime des restructurations donnent eux aussi droit à des impositions. Le régime de consolidation fiscale vise avant tout l’impôt sur les bénéfices des sociétés, cela dit les droits d’enregistrements, la taxe sur la valeur ajoutée, les cas de cessation du régime et les cas de sortie entrainent elles aussi des retraitements. Le groupe de sociétés peut être soumis à un contrôle fiscal en cas d’anomalies dans les déclarations fiscales. Company group’s taxation interests the business world and every taxpayer. Companies’ fiscal regime is very incentive to company creation. This type of regime is recent in Algeria. Its application regimes conditions, it is susceptible of revision. Algeria’s fiscal code has taken much from France’s general fiscal one. The determination of overall tax result is still a very large problematic. Tax result requires different adjustments. The transfer of profits and the regime of restructuring gives right to taxation. The tax consolidation regime aims primarily at taxing companies on their profits. Registration fees, the added tax value and cases of regime cessation, and cases of output causes retreatment. Company groups may be subject to tax control in case of anomalies in tax declaration.
Keywords: Account consolidation; Acte anormal de gestion; Consolidation des comptes; Consolidation fiscale; Division of taxation; Droit des sociétés commerciales; Fiscal consolidation; Fiscalité; Fiscalité des apports partiels d’actifs; Fiscalité des fusions; Fiscalité des scissions; Group of companies; Groupe de sociétés commerciales; Management act; Opérations de restructuration; Result owerall taw; Régime fiscal; Résultat fiscal d’ensemble; Tax; Tax asset partial contributions; Tax regime for restructuring commercial companies; Tax treatment of abnormal; Taxation of mergers; Taxe sur la valeur ajoutée; Transfer of profits to abroad; Transfert de bénéfices vers l’étranger; Value added tax

La renegociación de los contratos de asociaciones publico privadas - Montoya Hernández, Pedro Isaías (Universidad Nacional Mayor de San Marcos, 2017)
https://cybertesis.unmsm.edu.pe/item/39cd6fcb-324c-42c5-b321-b95dd135a2e1
Keywords: Administración pública; Contratos públicos; PPP; Partenariat public-privé

Şirketler topluluğunda hakimiyetin hukuka aykırı kullanılması - Özcanli, Fatma Beril (İstanbul Üniversitesi, 2017)
Şirketler Topluluğunda Hakimiyetin Hukuka Aykırı Kullanılması başlıklı çalışmamız ile 6102 sayılı TTK ile ilk defa pozitif düzenlemeye kavuşturulan şirketler topluluğu sorumluluk hukuku incelenmiştir. Kanun koyucu TTK m. 202 hükmü ile alelade hakimiyet bakımından, TTK m. 203 vd. hükümleri ile de tam hakimiyet bakımından hakimiyetin hukuka aykırı kullanılması ve sonuçlarını düzenlemiştir. TTK'nın şirketler topluluğuna ilişkin hükümlerinin önemli bir kısmı AktG sistematiği örnek alınarak oluşturulmuştur. Bu doğrultuda şirketler topluluğuna ilişkin TTK sistematiği incelenirken Alman doktrinine de sıklıkla başvurulmuştur. Çalışmamız kapsamında TTK m. 195 hükmünde düzenlenen kontrol araçları ve hakimiyet kavramı; yönlendirme, talimat ve yapısal karar alınması yoluyla hakimiyetin hukuka aykırı kullanılması; kayıp-denkleştirme sistemi; hakimiyetin hukuka aykırı kullanılmasından kaynaklanan sorumluluk, unsurları ve öngörülen talep hakları ayrıntılı olarak incelenmiştir. The new Turkish Commercial Code (TCC) Nr. 6102 has introduced the notion of "groups of companies" to the Turkish Commercial Law; hereby the "groups of companies" concept was spelled out for the first time in Turkish law. This thesis examines corporate group law in Turkey and demonstrates the intragroup responsibility regime in comparison with the German system. TCC Art. 202 foresee the consequences of unlawful exercise of control in basic dominance/control. Whereas TCC Art. 203-206 regulate the responsibility regime regarding the unlawful exercise of control with regards to full-control. Turkish corporate group law has been enacted under the big influence of the German AktG-System. Although our thesis focuses on the analysis regarding corporate group provisions of the TCC, the research on German law also covers a significant part of our thesis. This thesis examines in detail the control instruments stipulated in TCC Art. 195, the concept of control, the unlawful exercise of control by means of TCC Art. 202/1, TCC Art. 203 and TCC Art. 202/2, the concept of disadvantage and adjustment, the different liability regimes with regards to the category of the unlawful exercise of control and the rights of action.
483051
Keywords: Business union; Company law; Dominant position; Hakim durum; Hukuka aykırılık; Multicorporate enterprises; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Unlawful; İşletmeler topluluğu; Şirket toplulukları; Şirketler hukuku

La fonction de l’agent immobilier dans la vente d’immeuble achevé - Divoux, Jean-Pierre (Université de Lorraine, 2016)
Devant les remarques critiques dont fait l’objet la profession d’agent immobilier, il a paru intéressant à un agent immobilier à la retraite de faire le point sur la fonction de l’agent dans la vente d’immeuble achevé. Le sujet ne saurait se limiter au seul examen des rapports contractuels compliqués qui se nouent entre le vendeur, l’acheteur et l’agent immobilier. En effet, en menant à bien les projets de vente ou d’achat que lui confient ses clients, l’agent ne se contente pas d’accomplir la tâche d’un intermédiaire fiable sur un marché dont il a une bonne connaissance ; il devient véritablement un rouage structurant du marché immobilier. Naturellement, après l’étude du rôle de l’agent immobilier sur le marché immobilier, c’est son rôle dans le processus qui conduit à la conclusion du contrat de vente qui mérite de retenir l’attention, et cela depuis le moment où quelqu’un lui confie un mandat, qu’il soit de vente ou de recherche, jusqu’au moment où l’une des parties à la vente, mécontente de l’opération, se retourne contre l’agent immobilier
Keywords: Agents immobiliers; Droit immobilier; Immeubles; Immobilier; Vente et transmission; Vente immobilière

L’ordre juridique communautaire "OHADA" et les enjeux d’intégration du droit des affaires - Mikponhoue, Hervis Igor Cariol (Université de Perpignan Via Domitia, 2016)
Au lendemain de leur accession à l'indépendance dans les années 1960, les pays d'Afrique Francophone étaient dotés d'un système de droit privé étroitement dérivé de celui de l'ex-puissance coloniale. Pendant près de deux décennies, ces États ont fait évoluer séparément leurs législations conformément à l'expression de la souveraineté nationale même si la volonté d'unifier le droit en Afrique était matérialisée par des tentatives sous-régionales ayant peu abouti.Aujourd’hui, l’Organisation pour l’Harmonisation en Afrique du droit des Affaires(OHADA), créée depuis 1993 à Port-Louis œuvre pour une harmonisation du droit desaffaires en Afrique. Par l’adoption de ses divers actes uniformes, elle a su harmoniser voire uniformiser au plan communautaire les domaines essentiels du droit des affaires, notamment le droit commercial, le droit des sociétés et le droit des sûretés. Dans sa perspective d’intégration, elle envisage aussi d’énormes chantiers de codification afin d’étendre sa communauté à d’autres Etats encore réticents à une perte de leur souveraineté au profit d’une instance d’intégration et d’harmonisation du Droit des affaires.Dans la logique des objectifs poursuivis, nos premiers travaux de terrain ont porté sur l’ERSUMA étant donné qu’elle dispose d’une documentation très fournie sur l’OHADA, et que cette institution dont le rôle consiste à former les magistrats des divers Etats membres sur les textes communautaires, est ainsi le principal outil de vulgarisation des actes uniformes et des traités de l’organisation. Elle est donc l’une des instances les plus actives et les plusindispensables de l’OHADA.Retenons que cette perspective d’intégration de l’OHADA soulève encore d’énormesinterrogations relatives à la finalité des objectifs de l’Organisation, qui s’inscrit plus dans une perspective d’uniformisation que d’harmonisation comme le laisserait penser sa dénomination ; ajouté à l’épineuse question de la criminalisation des infractions en droit des affaires en Afrique et surtout à l’existence ou non d’un ordre juridique pour l’OHADA. Aussi, d’autres points importants, et diverses autres problématiques liées à l’intégration africaine du droit des affaires, ne présagent pas encore d’un avenir glorieux pour l’Organisation. Following their accession to independence in the 1960s, the countries of Francophone Africa were equipped with a system of private law closely derived from that of the former colonial power. During about two decades, these States have separately evolved their legislation in accordance with the expression of national sovereignty even if the desire to unify law in Africa was marked by sub regional attempts little successful. Today, the Organization for the Harmonization of Business Law in Africa (OHADA), created 1993 since in Port Louis works for business law harmonization in Africa. With the adoption of its various uniform acts, it has managed to harmonize or standardize at community level the essential areas of business law, including business law, corporation law and reliability law. In its perspective of integration, it is also considering consolidation sites in order to expand its community in other States which still reluctant to a loss of sovereignty for the benefit of an instance of integration and harmonization of business law. Let us remember that this OHADA integration perspective still raises huge questions regarding the purpose of the Organization's objectives, which fits more in a perspective of standardization over harmonization as its name would suggest; added to this sensitive issue of offenses criminalization in Business Law in Africa. Also, other important points and various issues related to African integration, which do not portent a glorious future for the Organization.
Keywords: Accountability or liability; Acte uniforme; Afrique francophone; Droit des affaires; Harmonisation; Harmonization; Integration's reform of OHADA; Reformes d’intégration OHADA; Responsabilité; Straight of business; Unification internationale; Uniform Act

Essai sur le formalisme contemporain dans la protection du consentement contractuel - Fortich, Silvana (Université Paris 2, 2016)
En matière de formation des contrats, le consentement de la partie qui s’oblige est soumis au principe de liberté des formes. Par exception, la volonté doit adopter une certaine forme contractuelle pour s’extérioriser. Face à l’évolution du droit des contrats et à la nécessité de combattre les déséquilibres contractuels propres aux rapports contractuels actuels, le formalisme expérimente un processus de revitalisation et de renaissance en droit contemporain dont la finalité principale consiste à protéger le consentement contractuel des parties au contrat. Cela rend indispensable l’analyse des fondements du formalisme et de son rôle dans la protection du consentement contractuel en droit contemporain, à travers la révision transversale de ses nouvelles manifestations, principalement en matière du droit de la consommation et du commerce électronique ; pour constater finalement ses véritables effets et conséquences en matière du droit des contrats. In contract law, the agreement of the parties is ruled by the freedom of choice of forms of contract. In this way, contracts are signed by the mere consent of the parties, and there is a freedom regarding the ways for its externalization. Despite this, the evolution of contract law and the need to combat specific contractual imbalances of contractual relationships, formalism is experiencing a revitalization process and a rebirth in contemporary law, with the main purpose to protect the contractual consent. For these reasons it is necessary to analyze the role of formalism in the protection of contractual consent, reviewing its new manifestations, mainly in the field of consumer and commercial law ; finally finding its true effects and consequences in contract contemporary law.
Keywords: Agreement; Consensualism; Consensualisme; Consentement; Consentement (droit); Consommateur; Consumers; Contract; Contrat; Contrats de consommation; Formalism; Formalisme; Formalité; Formalités (droit); Forms; Freedom; Information; Liberté; Liberté contractuelle; Mentions; Parties; Volonté

تأثير تغير الظروف على استقرار الثمن في عقود التجارة الدولية - موكه, عبد الكريم (جامعة مولود معمري, 2016)
Le thème de recherche porte sur la clause du prix en matière des contrats du commerce international, Cette étude qui tente d’y contribuer, porte essentiellement sur le domaine des pratiques contractuelles en droit des contrats du commerce international de longue durée, elle se propose de chercher les différentes techniques conventionnelles et juridiques pouvant maintenir la stabilité du prix et de chercher un moyen permettant de sauvegarder l’équilibre contractuel en dépit d’un bouleversement des données initiales causé par la survenances de circonstances nouvelles. Le prix est un élément essentiel dans la vie du contrat du commerce international sur lequel se focalise le consentement. Il est le centre de gravité du contrat international, mais vu la durée d’exécution des contrats internationaux et les différentes circonstances -imprévision ,force majeure et bouleversement économique- qui entravent la bonne exécution des clauses du contrat dont il est le prix, la modification et l’adaptation du prix devienne une nécessité imposée par les pratiques contractuelles et la jurisprudence arbitrale, cette révision ou réadaptation causé par l’impact de nouvelles circonstances imprévues permettra de sauver le contrat de sa disparition prématurée. Ainsi, le prix change de statut est devient élément secondaire qui varie en vertu des nouvelles circonstances, il remplit la fonction de protectionnisme pour maintenir la stabilité des contrats du commerce international.

Dealing with trade defence instruments in the context of economic integration in Africa - El Taweel, Khaled (University of Pretoria, 2016)
The launching of the T-FTA in June 2015 presents an opportunity for accelerating regional integration in Africa towards the establishment of a single market through deepening COMESA-EAC-SADC integration. This milestone can contribute positively to African development. Nevertheless, it faces different structural and technical challenges, including the risk of aggressive export strategies and unfair trade practices, which may wipe away a substantial part of the integration gains. This could undermine African integration plans and the largely infant industries in Africa, especially since many African countries lack sufficient technical skills, institutional capacity, and the legal framework to deal efficiently and effectively with unfair trade practices and to respond to situations which may require the application of emergency tools to better adapt to economic challenges. Apart from Egypt, Morocco, Tunisia, South Africa and Zambia national Trade Defence Instruments (TDIs) are not well developed. This could further constrain the ambitious African plans of economic integration. The thesis concludes that, although an effective TDI system is crucial for African integration as it can provide the required protection for African infant industries and unlock the potentials of African economic integration, the current African TDI systems are not effective. This is confirmed by the limited resort to TDIs in the African continent and the general perception that an effective TDI system is not a priority on the integration agenda. The concluded T-FTA TDI legal regime is not supportive for African integration plans in the long run. Africa should envisage how to upgrade its TDI system to make better use of the tools available under the WTO to deal with unfair trade measures, including anti-dumping to face dumped imports, countervailing measures to face subsidized imports, and safeguard measures to temporarily suspend concessions in the face of surge in imports. Africa can improve its national and regional TDIs system by learning from more developed TDI systems incorporated by other economic blocks such as the EU, NAFTA, Mercosur, and ASEAN. This thesis submits that the EU TDIs system is the most suitable to the African integration objectives. This submission is made while recognising the different level of development on both sides. The thesis submits that the long-term objective of the T-FTA is to have a regional investigating authority. It draws several recommendations to enhance African TDI system by working on five main categories: (A) The strategic direction; (B) The institutional framework; (C) Enhancing engagements; (D) Application of TDIs; and (E) The supportive factors.
URI: https://repository.up.ac.za/handle/2263/60043
Keywords: Economic integration; Trade defence instruments; Unfair trade practices

L'Acte Uniforme relatif au droit commercial général et le conflit des lois - Tamega, Paly (Université Paris-Saclay, 2015)
Le Traité pour l'Harmonisation en Afrique du droit des affaires a été signé à Port Louis (Île Maurice), le 17 octobre 1993 et, entré en vigueur le 18 septembre 1998. Il a été modifié par le Traité de Québec en date du 17 octobre 2008. Ce traité révisé est entré en vigueur le 21 mars 2010. Il a pour principal objectif de remédier à l'insécurité juridique et judiciaire existant dans les États parties. Pour ce faire, il aadopté neuf Actes uniformes dont l'Acte uniforme relatif au droit commercial général, ci-après l'AUDCG quifait l'objet de notre étude.Le Traité OHADA a également institué une Cour commune de justice et d'arbitrage chargée de l'interprétation et de l'application uniformes desdits actes. L'AUDCG a été adopté le 17 avril 1997et est entré en vigueur le 1er janvier 1998. Il a été modifié le 15 décembre 2010 et publié au Journal Officielde l'OHADA, le 15 février 2011. Il est entré en vigueur le 15 mai 2011.Il est applicable de la même façon dans tous les États contractants. L'existence d'un tel corpus de règles permet de réduire l'importance du fordans la résolution des litiges internationaux et de limiter la nécessité de recourir aux règles de conflits quigénèrent une certaine insécurité juridique. C’est la raison pour laquelle le droit OHADA de manière générale et l'AUDCG en particulier ne se préoccupe pas ou peu des conflits de lois. Pourtant,les conflits de lois subsistent dans l’espace OHADA. D’une part, l'AUDCG laisse subsister les dispositions du droit national du moment qu'elles ne lui sont pas contraires. L'AUDCG peut également faire l'objet de divergences d'interprétations par les juridictions nationales qui sont les juridictions de droit commun du droit harmonisé. Tout conflit d'interprétation est un conflit de lois. D'autre part, l'AUDCG s'insère dans un contexte normatif international caractérisé par une profusion de règles matérielles sous-régionales telles que l'Union Économique et Monétaire de l'Afrique de l'Ouest (UEMOA), la Communauté Économique des États del'Afrique de l'Ouest (CEDEAO), la Communauté Économique et Monétaire de l'Afrique Centrale (CEMAC) et internationales de droit matériel tels que la CVIM, le Protocole du 11 avril 1980 et la Convention de New-York du 14 juin 1974 relatifs à la prescription en matière de vente internationale de marchandises, la Convention de Genève sur la représentation en matière de vente internationale de marchandises. De cette imbrication de règles de droit naissent des conflits. Il persiste donc dans l'AUDCG des conflits de lois et desconflits de normes supranationales. La présente thèse a pour but d'étudier ces conflits ainsi que les principes de solutions qu'il convient d'y appliquer à travers les règles de conflit de lois, les Principes d'Unidroit, la loi d'autonomie, l'arbitrage.

حدود الأخذ بفكرة إعادة التفاوض في العقد - دراسة مقارنة - Henni, Abdellatif (Université Abou Bekr Belkaid, 2015)
حدودالأخذ بفكرة إعادة التفاوض في العقد
Keywords: التفاوض; العقد

Les situations de fait liées à une activité professionnelle : Étude comparée droit français - droit de l’OHADA - Alloume Okane, Olga (Université de Poitiers, 2015)
Les situations de fait liées à une activité professionnelle évoluent en marge du droit contrairement aux situations juridiques, où l'organisation est régulée par la loi ou les statuts. Elles se caractérisent d'une part, par des immixtions irrégulières dans la gestion au sein des groupements normalement constitués et d'autre part, par des activités non structurées exercées en groupe ou de manière individuelle, relevant souvent du secteur informel. Cette grande expansion des situations de fait a conduit le législateur français et le législateur africain de l'espace OHADA, à mettre en place des mesures incitatives, notamment la création des statuts d'auto-entrepreneur et d'entreprenant, respectivement, pour faciliter la création d'entreprise et formaliser progressivement leurs activités. Ces mesures pourraient permettre grâce à l'appui des pouvoirs publics et de divers organismes, de mieux adapter le droit des affaires aux réalités socio-économiques, particulièrement dans les pays de l'espace OHADA, où l'harmonisation du droit des affaires prendra probablement du temps, pour être effective. L'étude vise à rechercher en plus des solutions existantes, de nouvelles mesures qui pourraient contribuer à l'efficacité des programmes destinés à remédier aux situations de fait en général et, à régulariser le secteur informel en particulier.
Keywords: Acte de gestion; Acte uniforme; Activité informelle; Auto-Entrepreneur; Business law; Co-Emploi; Co-Employment; Direction de fait; Droit des affaires; Entreprenant; Entreprises en difficulté; Fact management; France; Informal activity; Management act; Pays de l'OHADA; Self-Employed person; Self-Promoter; Uniform Act

Regards sur le contrat de franchise - Bouvier, Amandine (Université de Montpellier, 2015)
Figure valorisée de la distribution, le contrat de franchise reflète une conception moderne du contrat où se conjugue différents caractères. Il est tout à la fois, un contrat de distribution en réseau qui s'intègre dans la catégorie des contrats de réitération, un contrat de financement et un contrat de collaboration. Le contrat de franchise est également une figure décriée de la distribution. Certaines difficultés liées à l'évolution de la législation et à celle de la jurisprudence alimentent les critiques à son encontre. De même, l'existence d'un déséquilibre informationnel et ce, dès l'origine de la relation contractuelle, peut conduire à créer un déséquilibre économique et éventuellement juridique entre les parties. Si la réglementation applicable au contrat de franchise ainsi que l'ensemble des clauses contractuelles contribuent à encadrer les rapports entre les parties au contrat, l'absence de régime juridique propre au contrat de franchise contribue, toutefois, au développement de contentieux en la matière. As an idea valued by distribution agreements reflect a modern understanding of the contract in which different characteristics are combined. It is at the same, a network distribution agreement, belonging in the category of reiterative agreements, a financing agreement, and a collaboration agreement. Franchise agreements are also an idea that is disparaged by ditribution. There are some challenges un connection whith changes in legislation and case law that feed the critiques against them. Likewise, the existence of an information imbalance at the start of the contractual relationship can lead to an economic, and possibly, a legal imbalance between the parties. While the regulations applicable to contract agreements as well as of the contractual clauses help to frame the relationship between the parties to the agreement, the absence of a legal system specific to franchise agreements contributes to the development of disputes on this topic.
Keywords: Circuits de distribution; Concessions (commerce de détail); Contrat de distribution; Contrats; Distribution; Distribution agreement; Franchise; Franchising; Franchising Agreement

Le licenciement économique dans les groupes de sociétés - Zarba, Catherine (Université d'Avignon, 2015)
Depuis le développement du capitalisme, la nécessité de créer un droit des groupes est apparue. Cette nécessité est corroborée par le fait qu’aujourd’hui, un salarié sur deux appartient à un groupe de sociétés. De plus, à l’aune de la mondialisation du contexte économique, le nombre de licenciements ne cesse d’augmenter. Certains groupes ont besoin de licencier pour sauvegarder leur santé économique, tandis que d’autres souhaitent prospérer. Ces derniers vont même jusqu’à l’abandon de leur filiale pour augmenter leur profit. Le législateur a institué une procédure de licenciement économique, applicable au groupe de sociétés, qui participe à une prévention des licenciements. Parallèlement, il a construit peu à peu un droit applicable à ce dernier dans le cadre d’une procédure individuelle et collective. Il a institué d’une part, l’obligation de rapatriement des salariés mis à disposition d’une filiale étrangère et, d’autre part, l’obligation de constituer un comité de groupe. Enfin, le groupe est tenu de contribuer à l’élaboration du plan de sauvegarde de l’emploi de ses filiales en fonction de ses moyens. Par ailleurs, l’existence d’un véritable droit des groupes dans le cadre d’une procédure de licenciement économique est confirmée par la position de la jurisprudence. En effet, le juge social est intervenu activement pour construire ce droit des groupes de sociétés. Tout d’abord, il a dégagé une obligation de reclassement élargie au groupe participant à l’édification de ce droit spécifique. Puis, la Chambre sociale a souhaité imputer une responsabilité au groupe en qualifiant la société donneuse d’ordre de coemployeur, ce qui permet de sanctionner le groupe de manière adaptée. Il existe donc un droit des groupes dans le cadre de la procédure des licenciements économiques participant à leur prévention, et intervenant lors dans leur mise en œuvre.
Keywords: Co-employeur; Economic redundancy; Group of compagnies; Groupe de sociétés; Licenciement économique; Licenciements économiques; Reclassement; Reclassification; Secteur d'activités

Le droit de la commande publique en Afrique noire francophone : contribution à l'étude des mutations du droit des contrats administratifs au Sénégal, au Burkina Faso, en Côte d'Ivoire et au Cameroun - Samb, Seynabou (Université de Bordeaux, 2015)
Tenaillé entre les logiques de la globalisation juridique, de l'intégration communautaire et les contraintes politiques, économiques et sociales propres aux Etats, le droit des contrats administratifs en Afrique noire francophone s'est transformé. Ses sources se sont élargies. Ses fondements conceptuels et matériels ont connu une mutation. C'est dans ce contexte qu'émerge le droit de la commande publique. Renouvelant les principes matriciels de transparence, de liberté et d'égalité, le droit de la commande publique apporte un noyau dur de règles communes aux marchés publics, aux contrats de délégation de service public et aux contrats de partenariat public-privée. Pour ce faire, il se fonde d'abord sur une nouvelle conceptualisation des notions à la base du droit des contrats administratifs. Dans un second temps, le droit de la commande publique représente une refondation des procédures de passation, des mécanismes de contrôle etde règlement des litiges relatifs à ces contrats administratifs. L'émergence de ces nouvelles règles fait suite aux réformes d'envergure des législations nationales relatives aux contrats administratifs. Cette étude se donne comme objectif d'analyser les apports véritables des dispositions issues de ces réformes afin de voir si elles ont permis de garantir davantage l'effectivité de l'idéologie concurrentielle. Caught between the new reality of legal globalization, community integrationrequirements and the political, economic and social constraints of each state, the regulation ofadministrative contracts in French-speaking African countries has changed. The sources of suchregulation have been expanded. Its conceptual and material foundations have changed. A newsystem of public procurement has emerged. Trying to renew principles of transparency, as wellas freedom of acces to public procurement and equality, the new public procurement regulationprovides a body of common rules for public procurement, public service delegation contractsand public-private partnership contracts.First, in order to achieve this, it relies on a new interpretation of the notions on whichAdministrative Contracts Law is based. Second, the new public procurement regulationrepresents a recasting of award procedures, control mechanisms and dispute resolutionmeasures. The emergence of these new regulations follows reforms of Administrative ContractsLaw in the respective countries.The objective of this study is to analyze the actual contribution of provisions flowing from thesereforms, in order to see if they are contributing to ensuring that competitive ideology isincreasingly effective.
Keywords: Afrique francophone; Arbitrage; Arbitragem; Arbitration; Autiroté de régulation des marchés publics; Commande publique; Competencia; Competition law; Concurrence; Contrats administratifs; Control mechanism; Contrôle à postériori; Contrôle à priori; Delegation of public utilities; Délégations de service public; Equality between bidders; Freedom of access to public procurement; Liberté; Marchés publics; Partenariat public-privé; Public procurement; Publice-private partnership; Regulation; Transparence; Transparency; Égalité

Le contrat d'adhésion entre professionnels - Briend, Cyril (Université Paris Cité, 2015)
Le professionnel que l'on croyait capable de défendre ses intérêts, par opposition au salarié ou au consommateur, s'est révélé tout autant victime de contrats déséquilibrés depuis quelques décennies. L'apparition de puissantes entreprises privées dans différents secteurs entraîne, de toute évidence, une inégalité entre les professionnels. Notre étude souligne la complexité de trouver un juste critère pour identifier de manière juste ce qu'est un professionnel partie faible. Il n'est pas possible de dire si, de manière générale, telle entreprise est plus puissante qu'une autre, car la personne morale partie au contrat peut cacher des intérêts difficiles à cerner au premier abord. Le juge ne peut pas non plus être l'arbitre autoritaire des prix sans risquer un détournement de sa fonction. Nous développerons le parti suivant : un contrat entre professionnels est dit d'adhésion lorsque celui-ci n'a pas donné lieu à une négociation idoine ; le juge doit alors s'efforcer de regarder le processus de pourparlers ainsi que les circonstances qui ont précédé la convention. De multiples critères peuvent aider le juge, tels que la taille de chaque entreprise, les parts de marché, les propos échangés par les parties, leur bonne ou mauvaise foi ou encore les efforts engagés par elles. Si le choix de l'analyse des négociations nous apparaît ultimement le plus juste, nous tiendrons cependant compte de ses limites. Il serait illusoire de penser que le juge peut toujours parvenir de manière certaine à connaître l'intégralité des circonstances antérieures au contrat. C'est pourquoi nous ajouterons à l'analyse des négociations un système de présomptions - quoique réfragables - lorsque la disproportion des prestations ou la différence de taille des entreprises ne laisse pas de place au doute. Nous mettrons enfin en lumière les stratégies employées par les parties fortes pour contourner cette analyse des négociations, comme des stipulations néfastes ou une tactique d'internationalisation. Il sera donc préféré une impérativité renforcée en droit national ainsi qu'en droit international. Une fois l'analyse des négociations effectuée, nous essayerons de proposer des sanctions à la hauteur du phénomène. Le juge, selon nous, doit être en mesure de modifier le contrat de façon souple, aussi bien de manière rétroactive que par un changement en cours d'exécution du contrat. Le caractère extrême de certains comportements contractuels nous incite à réfléchir à la possibilité d'un droit pénal plus dissuasif ou bien un droit « quasi pénal » sanctionnant ces comportements de manière plus appropriée. Néanmoins, c'est surtout au niveau de la procédure que se joue la protection contractuelle des professionnels. Un référé ajusté à cet objectif a tout lieu de répondre aux exigences de célérité qui gênent les parties faibles dans leurs démarches. Nous soulignerons aussi l'importance d'un système d'actions collectives qui surmontent efficacement l'écueil du coût du procès. À l'inverse, la sécurité juridique des entreprises nous conduira à proposer une procédure de protection par un système de droit doux. Première partie : L'identification du contrat d'adhésion entre professionnels. Deuxième partie : Le traitement judiciaire des contrats d'adhésion entre professionnels.
Keywords: ABUS; Abuse; Action collective; Adhesion contract; Advocacy; Arbitrage; Arbitragem; Arbitration; Autonomie de la volonté; Bargaining; Bargaining power; Business criminal law; Choice of law clause; Class action; Clause attributive de juridiction; Clause de choix de loi; Clause de procès; Competencia; Competition law; Concurrence; Conseil; Contractual autonomy; Contractual balance; Contrat d'adhésion; Contrats d'adhésion; Disproportion; Droit pénal des affaires; Droit spécial; Déséquilibre significatif; Entreprise; Evidence; Filiale; Hardship; Injonction structurelle; Interim measures; Interprétation in favorem; Jurisdiction clause; Laesio enormis; Legal personality; Lésion; Most favorable interpretation; Nullity; Nullité; Négociations; Ordre public; PME; Partie faible; Personnalité morale; Pouvoir de négociation; Preuve; Proceeding clause; Public order; Regulation; Rescrit; Responsabilité; Restrictions; Restrictive practices; Ruling; Référé; Régulation; Révision pour imprévision; SME; Significant imbalance; Special law; Structural injunction; Subsidiary company; Tort; Undertaking; Weaker party; Équilibre contractuel

La facture - Magnier-Merran, Kevin (Université de Strasbourg, 2015)
Document polyvalent, la thèse a pour ambition de démontrer que le détail juridique que la facture constitue en apparence, peut masquer des problématiques épineuses. La facture a été victime d'un détournement de fonction en raison de la pratique courante de l'insertion de données qui ne figureraient pas sur une facture rudimentaire. Il y a eu une inflation de la charge juridique contenue dans le document. C'est la possibilité du « phénomène contentieux » autour de l'acceptation d'une clause insérée dans la facture qui a permis à cette dernière d'intégrer la sphère contractuelle. Ce mouvement inflationniste s'est doublé d'une appropriation étatique du document. La juridicité du document a été renforcée par le législateur au nom d'un renforcement des conditions de libre concurrence conférant alors au document une dimension technique. Le document est alors marqué du sceau de l'autonomie, celle-ci menaçant alors d'autres droits fondamentaux et notamment, le principe de légalité, au nom d'une transparence invasive. La facture est alors sans aucun doute alors une image double. Ce qui saisit, c'est la trajectoire vécue par un document plus que polyvalent ayant pour point de départ une pratique naturelle et parvenant à un point d'arrivée technique et pesant. Le droit de la facture traduit fidèlement l'état d'un droit sous tension en ce que la législation obligatoire sur la facture est contraignante et ne répond pas aux exigences de sécurité juridique. Versatile paper, the thesis aims to demonstrate that the legal detail that the bill is apparently can hide thorny issues. The bill was the victim of a function of diversion due to the common practice of inserting data that do not appear on a rudimentary bill. There was an inflation of legal charge contained in the document. It is the possibility of '' disputes phenomenon '' around the acceptance of a clause in the bill which allowed the latter to integrate the contractual sphere. However, this movement is accompanied by another paradigm shift, when the legislature wished to seize the invoice into a competitive tool. Juridicity document has been strengthened by the legislature in the name of strengthening the conditions of free competition while giving the document a technical dimension. The document is then marked with the seal of autonomy, it then threatening other human rights, including the principle of legality, on behalf of invasive transparency. The invoice is then undoubtedly be a double image. What grabs is the trajectory experienced by a paper more versatile than having to base a natural practice and achieving a technical point of arrival and weighing. The right of the bill accurately reflects the state of a power law in that mandatory legislation on the invoice is binding and does not meet the requirements of legal certainty.
Keywords: Bill; Clause contractuelle; Contrats; Dimension contractuelle du document; Dimension technique du document; Droit des affaires; Electronic invoice; Facture; Facture électronique; Preuve; Preuve (droit); Price transparency; Principe de légalité; Principle of legality; Prix; Technical dimension of document; Transparence tarifaire

Grondslae van die reg op die reklamebeeld - Mostert, Frederick Willem (University of Johannesburg, 2015)
Keywords: Droit à l'image; Image rights; Publicidad; Publicitat; Publicité

عقد الاعتماد الايجاري الدولي - عسالي, عبد الكريم (جامعة مولود معمري, 2015)
Keywords: Contrats; Convention UTAR de 1988; Crédit-bail international; Droit des testaments; اتفاقية اوتارا لسنة 1988; الاعتماد الايجاري الدولي; العقود; قانون الارادة

Les femmes entrepreneures dans la société politique camerounaise - Nkolo Asse Sosso, Ginette Patience (Université de Bordeaux, 2015)
Avec le retour du multipartisme au Cameroun dans les années mil neufcent quatre-vingt-dix, l’État camerounais voit émerger des nouveaux acteursparmi lesquelles les femmes entrepreneures. L’objectif de cette thèse est dedéterminer quels enseignements structurels, les dynamiques sociopolitiquesdes femmes entrepreneures dans la sphère sociopolitique nous livrent sur lefonctionnement du système politique camerounais à l’aune du genre. A traversce questionnement, l’objectif est de voir dans quelle mesure l’entrée desfemmes en général et l’intégration des femmes entrepreneures en particulierdans le système politique entraînent un changement d’ethos de la vie politiquecamerounaise fortement imprégnée de l’ethos de la notabilité-séniorité et de lamasculinité et fortement caractérisée par la gouvernance de la manducation etla politique de l’autoreproduction. With the return to multi party system in Cameroon in the 1990s,Cameroon’s state witnessed the rise of new players, including womenentrepreneurs. This thesis aims at determining the structural lessons learnedfrom the sociopolitical dynamics of women entrepreneurs in social and politicalsphere about the functioning of Cameroon’s political system with regard togender. Through this inquiry, our goal is to see how the entry of women ingeneral and mainstreaming of women entrepreneurs in particular in the politicalsystem results in a change of ethos on cameroon’s political life which is stronglymarked by the ethos of notability-seniority and manhood and mainlycharacterized by the governance of manducation and policy of self-replication.
Keywords: Cameroonian political system; Cameroun; Coopt; Cooptation; Empowerment; Entrepreneurs; Femmes chefs d'entreprise; Femmes entrepreneures; Gender; Genre; Neopatrimonialism; Néopatrimonialisme; Patriarcat; Patriarchy; Political reproduction; Politique et gouvernement; Representations; Reproduction politique; Représentations; Resources; Ressources; Strategies; Stratégies; Système politique camerounais; Women

Contratos de aliança: direito empresarial e ambiente cooperativo - Silva, Leonardo Toledo da (Universidade de São Paulo, 2015)
A presente tese realiza uma análise interdisciplinar dos contratos de aliança, arranjos colaborativos desenvolvidos a partir do início da década de 90, cujo objetivo é a implantação de projetos complexos industriais e de infraestrutura. Este trabalho investiga a percepção do autor de que o modelo proposto pelos contratos de aliança, em regra, promove um esvaziamento voluntário da função do contrato como ferramenta de aplicação, ainda que potencial, de sanções a comportamentos culposos, justamente com o fim de não prejudicar a construção natural de uma relação cooperativa. Busca-se ainda compreender a função desempenhada pelo contrato e pelo direito contratual, nesse contexto colaborativo, e qual a relação entre os mecanismos formais e informais de garantia de cumprimento contratual. Sustenta-se que, nesse universo, o aparato formal do contrato auxilia as ferramentas informais de enforcement, fornecendo o arcabouço de troca de informações essencial à criação endógena de confiança. Ademais, a fim de não prejudicar o ambiente cooperativo, sustenta-se a aplicação de sanções contratuais formais somente em situações excepcionais, geralmente caracterizadas pelo elemento de quebra de confiança. Sugere-se, ao longo da tese, que uma abordagem processual de regulação do contrato a qual permite sanção de comportamentos que descumpram o procedimento contratual acordado seria mais adequada do que uma abordagem estritamente substantiva que proteja a relação inicial de troca. Ao final, amparada pelas percepções construídas ao longo da pesquisa, é realizada uma reflexão jurídico-dogmática, na qual, após a contextualização jurídica dos contratos de aliança, lhes são sugeridas interpretações de aplicação de conceitos da teoria obrigacional, e de ferramentas de organização de interesses intracontratuais, como a boa-fé, o conflito de interesses e os deveres fiduciários. This thesis conducts an interdisciplinary analysis of project alliancing, collaborative arrangements developed as of the beginning of the 90s, whose goal is the implementation of complex industrial and infrastructure projects. This work investigates the perception of the author that the model proposed by alliance contracts, in general, promotes a voluntary emptying of the role of the contract in punishing, even potentially, unintentional contractual defaults, as a means of not harming the natural construction of a cooperative relation. The work seeks to understand the role played by the contract and the contractual law, in such collaborative environment, and what is the relation between formal and informal mechanisms of contractual enforcement. It argues that, in this universe, formal contractual apparatus supports informal contractual enforcement mechanisms, providing a governance framework that allows information exchange, which is essential to the endogenous creation of trust. Moreover, in order not to jeopardize the cooperative environment, this thesis suggests the suitability of formal contractual punishment only in exceptional circumstances, often characterized by the breach of trust. It is suggested, along the thesis, that a procedural approach of contract regulation which allows punishment of behaviors that deviates from agreed contractual procedures may be more suitable than a strictly substantive approach that protects the initial exchange relation. At the end, supported by the perceptions constructed along the research, some legal-dogmatic considerations are made, in which, after legally qualifying the alliance contracts, it is suggested to it some applicative interpretations of concepts of obligational theory, and organizational tools of intracontractual interests, such as good faith, conflicts of interest and fiduciary duties.
Keywords: Alliance contracts; Boa-fé; Collaborative contracts; Construction; Contracts; Contractual governance; Contrat d'alliance; Contratos; Cooperation; Cooperação; Crowding out; Good-faith; Informal enforcement; Joint responsibility; Relational contracts; Risk sharing

La pratique du montage contractuel : réflexion sur une figure juridique en construction - Diagne Ndir, Ndèye Sophie (Université Cheikh Anta Diop, 2015)
Keywords: Contrat (montage); Droit des contrats; Fraude

İslam ticaret hukukunda cehalet ve güncel akitlere etkisi - Aslan, Bedri (Dicle Üniversitesi, 2015)
Türk Hukuku'nda navlun (deniz yolu ile eşya taşıma) sözleşmeleri; yolculuk çarteri sözleşmesi ve kırkambar sözleşmesi olmak üzere iki ana gruba ayrılmıştır. Bunlardan çarter sözleşmeleri arızi deniz taşımacılığında, kırkambar sözleşmesi ise genellikle düzenli hat taşımacılığında kullanılır. Günümüzde deniz taşımacılığında yaşanan gelişmelerin sonucu olarak düzenli hat taşımacılığının ve kırkambar sözleşmesinin önemi artmaktadır.Bu tezde; Türk Hukuku'nda kırkambar sözleşmesi kavramı, sözleşmenin asli unsurları, özellikleri, benzer sözleşmelerle karşılaştırılması, sözleşmeye uygulanacak hükümlerin tespiti gibi konuların yanında sözleşmenin tarafları, ilgili kişileri, sözleşmenin ifasında yer alan yardımcı kişileri, tarafların hak ve yükümlülükleri ve sözleşmenin sona ermesine değinilmiş Türk Ticaret Kanunu ve diğer mevzuat hükümlerinden, ilgili uluslararası andlaşmalardan, ticari örf-adet kurallarından, yüksek mahkeme kararlarından, öğretiden, uygulamada kullanılan tip sözleşme ve konişmento örneklerinden yararlanılmıştır. In Turkish Law, contracts of affreightment are divided into two main cathegories which are; voyage charter and contract of common carriage of goods. While the former is being used in tramp shipping, the latter is being used in liner shipping. As a result of recent developements in carriage of goods by sea, the importance of liner shipping and contract of common carriage of goods has been rising.This thesis is based on; Turkish Commercial Code, other related national regulations and international agreements, customs, decisions of high courts, doctrine, mostly used standard contract and bill of lading forms. In this thesis; the chracteristics, parties, differences from other contracts, rights and obligations of the parties and termination of contract of common carriage of goods have been analysed.
Tez N°429811
Keywords: Affreightments; Commercial law; Contract of Common Carriage of Goods by Sea; Contract of carriage; Deniz hukuku; Deniz ticareti; Deniz yolu taşımacılığı; Kırkambar Sözleşmesi; Law of the sea; Navlun sözleşmeleri; Sea trade; Sea transportation; Taşıma sözleşmesi; Ticaret hukuku; Turkish commercial law; Türk ticaret hukuku

Kayıtlı sermaye sistemi - Cenkci̇, Esra (Akdeniz Üniversitesi, 2015)
Sermayenin yönetim kurulu kararıyla artırılması esasına dayanan kayıtlı sermaye sistemi, daha hızlı ve daha az masrafla ortaklığın sermayesinin artırılmasını amaçlar. 2499 sa. SerPK' den bu yana halka açık anonim ortaklıklara özgü bir kurum olarak Türk hukukunda uygulanmakta olan sistem, TTK ile birlikte halka açık olmayan anonim ortaklıklar için de uygulanabilir hale gelmiştir. Aynı esaslara dayandığı ve aynı amaca hizmet ettiği için kurumun, TTK ve SerPK' de ayrı ayrı düzenlenmesine lüzum yoktur. Sistem, yönetim kurulunun usulüne uygun olarak sermayenin artırılması konusunda yetkilendirilmesi suretiyle ortaklık açısından uygulanabilir hale gelir. Yetkilendirme işlemleri esas sözleşme değişikliğini gerektirir. Yönetim kurulunun sermayeyi artırma yetkisi, esas sözleşmede gösterilen kayıtlı sermaye ve yetki süresiyle sınırlıdır. Bu sınırlara ulaşılmışsa ve esas sözleşmeyle yeni yetki sınırları tespit edilmemişse, yönetim kurulu sermaye artırım kararı alamaz. Öte yandan, bu yetkilendirmede yönetim kuruluna, sermaye artırım yetkisi yanında sermayenin artırılmasıyla bağlantılı olup kanunda izin verilen konularda da yetki tanınabilir. TTK ve SerPK' deki ilgili hükümler incelendiğinde, kayıtlı sermaye sisteminde sermaye artırım kararının, esas sermaye sisteminde olduğu gibi, esas sözleşme değişikliği olarak kabul edildiği görülmektedir. Bu düzenlemeler, sadece genel kurulun toplanıp karar alması işlemleri için gerekli olan zamandan ve masraftan tasarruf edilmesini sağlar. Kayıtlı sermaye sisteminin daha etkin bir kurum olarak kullanılması, esas sözleşme değişikliğine ilişkin işlemlerin de bertaraf edilmesini gerekli kılar. Anahtar Kelimeler: Sermaye, Kayıtlı Sermaye, Sermaye Artırımı, Yönetim Kurulu, Anonim Ortaklık. The registered capital system is based on increasing the capital with decision of board aims to increase the company's capital faster and less costly. System that is applied in Turkish Law as an institution special to public companies since CMC no: 2499, becomes applicable for non-public companies with TCC. As based on the same principles and serves the same purpose, there is no need to regulate the institution in TCC and CMC separately. System becomes applicable in terms of company, by duly authorization the board concerning capital increase. Authorization procedures require amendment of company's article. Authority of capital increase of board is limited with the registered capital and authority period that are shown in company's article. When it reached this limits and determined any new authority limits with the company's article, board can not take a decision on capital increase. On the other hand, in this authorization, board also can be authorized on the issues that are in connection with capital increase and permitted by act, in addition to the capital increase authority. When analyzed the related provisions in TCC and CMC, it is seen that the capital increase in registered capital system, as in ordinary capital system, is accepted as company's article amendment. These regulations provide to save only from time and cost that are required for procedures to take decision of general assembly. Using the registered capital system as more effective institution requires to eliminate the procedures related to amendment of company's article. Keywords: Capital, Registered Capital, Capital Increase, Board of Directors, Joint Stock Corporation.
Keywords: Anonim ortaklıklar; Board of directors; Capital increase; Capital social; Incorporated companies; Kayıtlı sermaye sistemi; Registered capital system; Sermaye artırımı; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Yönetim kurulu

Essai sur la justice contractuelle : contribution à l'étude des fondements théoriques de la protection de la partie vulnérable - Manekeng Tawali, Joelle (Université Laval, 2015)
Dans un contexte socio-économique dominé par la rapidité et la complexité des échanges, le sort du contractant est très souvent déterminé par sa position de vulnérabilité. Quelles formes prend cette vulnérabilité ? Quelles sont les idéologies, les valeurs et les critères de justice à partir desquels les mesures protectrices ont été édictées et mises en œuvre ? Ceux-ci tiennent-ils adéquatement compte de la vulnérabilité des parties ? Quelle place lui réservent les différentes réponses apportées par le droit des contrats ? Telles sont les questions sur lesquelles porte la présente étude sur la justice contractuelle dont l’objectif est de procéder à une analyse critique des fondements de la protection de la partie vulnérable. Ces derniers ne révèlent pas nécessairement l’existence d’une logique d’ensemble. Dans une perspective idéaliste, la moralité contractuelle et l’utilité économique du contrat sont les bases sur lesquelles la protection de la partie vulnérable a été envisagée. Appréhendée sur un plan individuel, la vulnérabilité du contractant repose sur l’idée d’une justice essentiellement réparatrice. Celle-ci est axée sur le respect de la bonne foi contractuelle et sur le désir de donner à chacune des parties les moyens de défendre ses intérêts. C’est donc de manière exceptionnelle que la vulnérabilité sera prise en compte. En réaction aux limites d’une protection faisant de l’existence d’un comportement fautif la condition de l’octroi de la protection, une vision réaliste de la sauvegarde des intérêts légitimes du contractant vulnérable a été mise de l’avant. Elle prend appui sur la dimension collective de la vulnérabilité du contractant. Il en résulte un régime de protection fondé sur la notion de relation et sur une conception objective de la justice. Toute chose qui se traduit soit par une protection technico-formaliste, soit par l’idée de solidarité faisant du contrat le lieu d’une communauté d’intérêts. Cependant, cette approche du contrat n’intègre pas forcément l’importance du rôle réservé à la volonté, ni les diverses catégories de contrats.
Keywords: Contrats; Responsabilité (droit); Responsabilité contractuelle

The complex case for another hard look : transnational pharmaceutical regulation and the pedagogical role of courts - Rizzi, Marco (European University Institute, 2015)
The thesis argues for a 'pedagogical' role for courts in the US and EU in ameliorating the increasingly transnational regulation of pharmaceutical product safety through complementary monitoring of the outputs of regulatory processes. The study is divided into two parts. First, the thesis explores the regulatory institutional design in the US and EU. The parallel development of the FDA and EMA suggests that both markets have achieved consolidated domestic/regional regulatory frameworks, which do however show multiple weak spots. These vulnerabilities are aggravated by a strong push towards transnationalisation of regulatory procedures: domestic systems are now permeated by potentially disruptive exogenous elements (e.g. the ratification of transnationally negotiated protocols and increasing reliance on foreign clinical trials data). The thesis explores issues of effectiveness of safety delivery and legitimacy of rule-making processes to suggest scope for improvement in both areas. The second part considers the potential contribution of the judiciary, particularly national courts in the US and EU, to investigate whether the exercise of complementary judicial governance can enhance the effectiveness and legitimacy of an otherwise essentially closed and self-perpetuating system. A selection of cases grounds the claim that, through liability litigation, courts have the capacity to improve the safety levels delivered by regulation and thereby to contribute to output-based legitimacy of the institutional design. This claim is tested in light of acknowledged strengths and limitations of court processes and with regard to differentiating elements at the national level, particularly regarding access to justice. The concluding argument reassembles the results of the study to recommend the existing tool of domestic litigation as a response to certain vulnerabilities in pharmaceutical regulation. The 'hard look' doctrine described by Sheila Jasanoff grounds the normative claim for a 'pedagogical' role for courts, enhancing regulation beyond the outcome of isolated cases – ad adiuvandum rather than contra.
Accepted: 2015-11-04T16:35:28Z
Keywords: Drugs; European Union countries; Pharmaceutical industry; Pharmaceutical regulation; Pharmaceutical right; United States

Public-private cooperation in transnational regulation - Schmidt, Rebecca (European University Institute, 2015)
This thesis examines the emergence of transnational regulatory cooperation between public and private actors. It inquires why a private regulator and an international organisation may enter into a cooperation agreement in order to regulate particular issues, and what this tells us about the relationship between ‘expertise,’ ‘authority’ and ‘legitimacy’ in particular domains of global governance. The argument put forward in the thesis is that different types of regulators cooperate because, in an unsettled global space with no hierarchical framework, it is necessary for them to acquire sufficient authority to secure compliance with their regulatory agenda. In order to acquire and maintain such authority, regulators must be perceived as legitimate and their regulation as effective. Cooperation can open venues for participation and deliberation and for the exchange of necessary competences (particularly expertise); and thus ultimately can help regulators establish and strengthen their authority. Another important finding of this research is that cooperation can develop into more long-lasting network structures. These networks are often of a multi-level nature. As such, they traverse local, national, and international spaces. The thesis then develops the idea of ‘networks of constitutionalization’ to describe the observation that bilateral arrangements as examined here generate ordering effects which extend beyond the two parties. Consequently they become the basis for norm creation and adoption for different types of actors located in the networks formed around the issue area. Thus, even in pluralistic structures, eventually a certain kind of constitutionalization can emerge putting into question sharp divisions between ‘pluralist’ and ‘constitutionalist’ interpretations of a developing global (legal) order. This work also encompasses two case studies: the ISO 26000 process, whereby the ‘private’ technical standard setter ISO concluded separate cooperation agreements with the ILO, the OECD and the UN Global Compact; and a case study on ‘Sport and Environment’ that focuses on the long-standing cooperation between the IOC and the UN Environmental Programme.
Accepted: 2015-04-16T14:24:52Z
Keywords: International Law; Law and Globalization

La responsabilité de la société mère du fait de ses filiales - Ouassini Sahli, Meriem (Université Paris 9 Dauphine, 2014)
En principe, les sociétés intégrées à un groupe sont juridiquement indépendantes et sont des sociétés comme d’autres, jouissant de la personnalité morale, et participant à la vie juridique comme tout sujet de droit. Cette indépendance juridique de principe concorde mal avec la réalité caractérisée par le contrôle exercé par la société mère, chef de groupe, et qui est dicté par la communauté d'intérêts qui cimente le groupe, il y a une asymétrie entre la situation de fait et la situation de droit. La responsabilité du groupe ne pouvant, de fait, pas être engagée, l’autre option est la recherche de la responsabilité de la mère, en sa qualité de société contrôlante, lorsqu’un acte dommageable a été commis par sa filiale. Toutefois, la notion d’autonomie pose un écran juridique très résistant qui protège la mère de toute action menée à son encontre du fait de ses filiales. Par principe, la responsabilité de la société-mère pour les faits de sa fille ne peut donc être recherchée.Par ailleurs, les groupes de sociétés présentent généralement la particularité d’être marqués par le sceau de l’extranéité, en raison de leurs activités qui se déploient bien souvent au-delà des seules frontières nationales, ce visage transnational de l’activité des sociétés rend plus difficile la responsabilisation de la société mère pour les actes commis par ses filiales, il faut, effectivement, dire que le droit international public, n’est pas en mesure de développer un système de responsabilité globale pour des cas de dommages trans-frontières.
Keywords: CSR; Civil liability; Criminal liability; Droit souple; Exterritorialité; Extraterritoriality; Extraterritorialité; Filiales; Group of Companies; Groupe de sociétés; Groupes de sociétés; Holdings; Intérêt social; Personnes morales; Principe de l’autonomie de la personne morale; Principle of self-Responsibility; RSE; Responsabilité civile; Responsabilité pénale; Responsabilité sociétale; Social interest; Sociétés écran; Soft law; Theory of transparency; Théorie de la transparence

Aspectos jurídicos de la práctica profesional del diseño de interiores - Rovira Serrano, Maria del Pilar (Universitat de les Illes Balears, 2014)
Esta tesis se sustenta sobre la hipótesis de que el diseño de interiores es una ocupación técnica liberal regulada, titulada y no colegiada, aunque vacía de contenido legal (obligaciones y responsabilidades) más allá de lo que dispone el Real Decreto 902/1977, de 1 de abril, regulador de las facultades profesionales de los decoradores, una disposición normativa obsoleta y conflictiva, pero la única que regula sus atribuciones. Para dotar a este colectivo del necesario contenido legal se han analizado tanto las principales normas jurídicas como la doctrina y jurisprudencia española; un análisis centrado en la formación, atribuciones, corporativismo y contratación (elementos, prueba, interpretación, obligaciones, incumplimiento y resolución del contrato). En el apartado de conclusiones se ha validado la hipótesis inicial, al tiempo que se ha expuesto la necesidad de un nuevo marco normativo, adaptado a la realidad de esta profesión, que expresamente incluya al interiorista como técnico competente en la edificación.
URI: https://www.tdx.cat/handle/10803/288312
Keywords: Civil Law; Derecho Civil; Derecho Mercantil; Derecho Privado; Derecho privado; Design; Diseño; Diseño de Interiores; Disseny; Disseny d’Interiors; Dret Civil; Dret Mercantil; Dret Privat; Interior Design; Private Law; Trade Law

La gestion des risques juridiques bancaires : étude appliquée aux obligations d'information, de mise en garde et de conseil - Varnav, Mihaela (Université Paris 1, 2014)
Les banques sont exposées à une multitude des risques. Dans un contexte réglementaire caractérisé par le renforcement de la surveillance européenne et des règles de protection de la clientèle, il est nécessaire de cartographier, évaluer, contrôler et maîtriser le risque juridique bancaire, partie intégrante du risque opérationnel. Pour ce faire, la récente discipline de gestion des risques ou risk management fournit les outils nécessaires aux établissements de crédit. Sa méthodologie générale s'avère pleinement transposable en matière juridique et est adaptée aux exigences légales en matière de contrôle interne, de gestion des risques et de calcul d'un niveau équilibré et approprié de fonds propres. Elle offre, par ailleurs, une grille de lecture inédite des obligations d'information, de mise en garde et de conseil du banquier à l'égard de ses clients. Véritable manifestation du paradigme ordo-libéral, ce trio informationnel témoigne du fait que le droit ne peut pas faire abstraction du milieu économique et social. Utiles pour le bon fonctionnement du marché et pour le progrès social, elles sont en même temps le signe d'une tendance au rééquilibrage contractuel, en dépassant la conception classique d'égalité abstraite des parties contractuelles. Les risques juridiques liés à ces trois obligations du banquier envers ses clients sont nombreux, pouvant être à la fois fréquents et extrêmes. L'étude de ces risques permet, entre autres, d'identifier les excès, voire les ambiguïtés ou les insuffisances du droit positif en la matière. Banks are exposed to a multitude of risks. In view of the increased focus on European supervision and on consumer protection in the current regulatory framework, it is appropriate to map, evaluate, monitor and control the banking legal risk, as part of the operational risk. For this purpose, the risk management offers the necessary tools to the credit institutions. Its general approach is completely applicable in the legal field and is adapted to the legal requirements on internal supervision, risk management and determination of a balanced and proper level of own funds. Moreover, it provides a new key for the reading of the duties to disclose information, to caution and to advise that the banks have towards their clients. As a genuine expression of the ordo-liberal paradigm, this triple duty demonstrates that the law cannot ignore the social and economic. These duties are useful for the proper functioning of the market and for the social progress, and they are also the sign of a trend towards resetting the balance in contracts, leaving behind the classic concept of theoretical equality between parties to a contract. There are many legal risks in relation to those three requirements of the bank towards its customers, which can have frequent occurrences and very serious consequences. The study of those risks is meant, inter alia, to identify the overregulation, the ambiguities or the lack of regulation in the current legal framework.
Keywords: Banque; Banques; Compliance; Conformité; Contrôle bancaire; Divulgation d'informations; Droit; Droit belge; Droit européen; Droit fançais; Etablissement de crédit; Gestion des risques juridiques; Gestion du risque; Legal risk management; Obligation d'information; Obligation de conseil; Obligation de mise en garde

Nombre Comercial. Coordinación Normativa y Registral con la Denominación Social. Su Tránsito hacia la Marca de Servicio - Ham Juárez, Jesús Alejandro (Universitat de Barcelona, 2014)
A lo largo de la historia las figuras nombre comercial y denominación social han compartido características similares, tales como el hecho de que ambas están destinadas a individualizar e identificar: el nombre comercial a una persona física o jurídica, en el desarrollo de su actividad empresarial para distinguirse de actividades idénticas o similares en el tráfico económico; la denominación social, en cambio, a una sociedad mercantil o asociación en el tráfico jurídico. Es decir, ambas figuras tienen el común denominador de ser expresiones que componen un elemento de identificación de las empresas y personas jurídicas en el tráfico económico y jurídico, respectivamente. En virtud de lo anterior, este trabajo tiene como objetivo primordial hacer un análisis jurídico de lo que debe entenderse por nombre comercial y por denominación social, así como plantear de manera sucinta la problemática que al respecto impera; por qué cuerpos normativos se encuentran reguladas las figuras de referencia; las autoridades administrativas encargadas de llevar un registro de unos u otras, así como de las posibles, y en cierto modo comunes, controversias que surgen entre sí, a pesar de que doctrinalmente tengan conceptos y funciones perfectamente delimitados y distintos. Se hará también una breve alusión a la figura del nombre comercial o su institución equivalente con otros países para tener elementos de comparación entre unos y otros. El método elegido para la elaboración de este trabajo ha sido un análisis de la normatividad y jurisprudencia española; fuentes bibliográficas, hemerográficas y electrónicas, así como sentencias y resoluciones dictadas en relación con la materia. Para ello se ha realizado una actividad analítica y de contraste entre nombres comerciales y denominaciones sociales y, siendo éstos los objetivos concretos, se han evitado distracciones o desvíos de atención en diversos temas que fueron surgiendo durante el transcurso de esta investigación. El contenido de este trabajo está desarrollado siguiendo un planteamiento por capítulos. En los capítulos primero y segundo se hace un análisis jurídico de las figuras nombre comercial y denominación social, detallando sus conceptos, funciones, clases, requisitos indispensables, naturaleza jurídica, acciones de defensa que el titular de un nombre comercial podrá ejercer, entre otras, para sentar las bases y poder entender los conflictos que pueden y que llegan a surgir entre unos y otras. En el capítulo tercero se hará una somera reseña de las figuras equivalentes al nombre comercial español en Derecho comparado, tanto en Italia, como en el Reino Unido y en México, es decir, la ditta, la trade mark y el nombre comercial, respectivamente, para con ello tener elementos de análisis jurídico y comparativo entre éstos tres y el primero. El propósito del capítulo cuarto será, precisamente, analizar y detallar las causas que originan las controversias entre nombres comerciales y denominaciones sociales, haciendo alusión a los diferentes supuestos que en la vida cotidiana acontecen, además de explicar la forma en que dichas controversias son dirimidas. En el quinto y último capítulo de este trabajo de investigación, se hará una descripción del apartamiento conceptual, funcional y normativo entre los nombres comerciales y las denominaciones sociales, además se plantean ciertas medidas y reformas legales que, de llevarse a cabo, acercarían a dichas figuras, clarificarían su situación actual y homogeneizarían los conceptos que habrán de utilizar, por un lado, la OEPM y, por el otro, el RMC al momento de otorgar la concesión del registro de nombres comerciales (o marcas de servicio) y de denominaciones sociales, respectivamente.
URI: https://www.tdx.cat/handle/10803/145977
Keywords: Business names; Ciències Jurídiques; Commercial law; Derecho mercantil; Dret mercantil; Econòmiques i Socials; Industrial property; Intellectual property; Marcas registradas; Marques de fàbrica; Nombres comerciales; Noms comercials; Propietat industrial; Propriedad industrial; Trademarks

Substantive equality, affirmative action and the alleviation of poverty in South Africa : a socio-legal inquiry - Katiyatiya, Luyando Martha (Stellenbosch University, 2014)
Substantive equality is a constitutional imperative, hence the need for strategies that attempt to realise it for the sake of genuine social reconstruction. The principle of equality runs through all other rights in the South African Constitution. Be that as it may, equality is an elusive concept, which makes its achievement an ambitious task. Nonetheless, there are strategies that attempt to bring to the fore the ‘substance’ of the concept in order to ensure the actual realisation of socio-economic benefits. Such strategies include, among others: social security, education, economic empowerment, skills development and affirmative action. This study will focus on the latter of these strategies, namely affirmative action. Although affirmative action is practised around the world, one of the (many) criticisms of the policy is that it fails to bring about substantive or structural change. In other words, it may change the racial and gender composition of the classroom or the workplace, but does not address the challenges that cause the disadvantages of marginalised groups in the first place. It is arguable that affirmative action has increased inequality in South Africa by benefiting the apex of the class structure and not the majority of the population living in abject poverty. This study develops a theoretical analysis of the link between status (race, sex and ethnicity) and socio-economic disadvantage, and the central question that the study addresses is the following: How can the policy of affirmative action be redesigned to ensure that it benefits the socio-economically disadvantaged? A secondary question that is investigated is whether affirmative action can contribute to the development of human capacities in the context of poverty alleviation. It is arguable that substantive equality facilitates the adoption of strategies (such as affirmative action) to address socio-economic inequality, poverty and social exclusion. The research suggests that a paradigm shift is necessary in order to reconceive of affirmative action as a policy that does not only focus on ensuring ‘equitable representation’ of disadvantaged groups in the workforce or the classroom, but also provides for the development of human capacities. This can be achieved if one adopts an expansive view of affirmative action and if one utilises class as one of the numerous criteria for determining the beneficiaries of the policy.
URI: http://hdl.handle.net/10019.1/86607
Keywords: Affirmative action programs; Equality before the law; Politics and government; Public welfare; Social conditions; South Africa

La procédure de data-room dans la vente d'immeubles affectés à une activité commerciale - Faurel, Maxime (Université Paris-Est, 2014)
Depuis plusieurs années, la procédure de data-room s'est imposée auprès des professionnels de l'investissement comme le mode privilégié de vente d'immeuble leur permettant d'organiser efficacement la rotation de leur patrimoine. Juridiquement, cette procédure se déroule en deux phases. La première, précontractuelle, imposera aux candidats-acquéreurs, de déterminer la valeur de l'immeuble suite à un audit de chacune de ses composantes (juridique, financière, environnementale, technique, fiscale), puis de formuler à une date convenue entre les parties une offre ferme d'achat. La seconde, contractuelle, permettra au candidat-acquéreur retenu par le vendeur de finaliser, par la rédaction d'une promesse puis de l'acte authentique, les conditions de réalisation de la vente.Le recours à une telle procédure n'est pas exempt de risques. D'une part, dans le silence de la loi, elle n'est soumise à aucun régime spécifique et relève donc du droit commun de la responsabilité civile (délictuelle et contractuelle) et plus exceptionnellement de la responsabilité pénale. D'autre part le foisonnement de normes juridiques que doivent maîtriser les candidats-acquéreurs lors de la valorisation de l'immeuble peut induire un risque d'erreur dont la conséquence économique est une surévaluation du prix d'acquisition.Pour parvenir à maîtriser ce double niveau de risque que nous qualifierons de juridique et d'opérationnel, il a fallu dans un premier temps déterminer le régime de responsabilité dont relève cette procédure et ce à chacune de ces phases, puis dans un second temps analyser le déroulement de la phase d'audit en vue de proposer un modèle le plus exhaustif possible.
Keywords: Data-Room; Immobilier (droit); Maîtrise; Risque; Vente d'immeuble

Le droit uniforme africain et le droit international privé - Adouko, Anoh Bernard (Université Bordeaux 4, 2013)
Que l’on appréhende le droit uniforme sous l’angle du droit international privé ou que l’on mesure les incidences de la vision communautaire du droit uniforme sur l’évolution du droit international privé des Etats membres, les interactions entre droit uniforme africain et droit international privé peuvent se résumer aux constats suivants. La simple uniformisation du droit entre des Etats se révèle insuffisante à éliminer ou à résorber les conflits de lois et au-delà l’ensemble des difficultés suscitées par l’élément d’extranéité à savoir les conflits de juridictions, la condition des étrangers … Les raisons en sont notamment que l’unification du droit (règles de fond et règles de procédure) n’a jamais pu être totale, des points irréductibles pouvant se révéler insurmontables au stade de la conception des règles uniformes mais aussi l’uniformisation pouvant s’altérer par la suite, lors de son application, du fait de divers facteurs. Les législateurs supranationaux ont donc dû accompagner, le plus souvent, les règles uniformes de fond de règles uniformes de droit international privé de sorte qu’on conclut, en droit uniforme africain, à l’émergence d’un droit international privé d’origine communautaire. Secrété par un droit, lui-même spécifique, se situant à l’intersection du droit international et du droit interne, du droit public et du droit privé, le droit international privé issu du droit uniforme africain sera lui aussi nécessairement spécifique dans sa conception, dans ses méthodes, outils ou instruments même s’il fait preuve à certains égards d’un certain classicisme. Son avènement a bouleversé les assises du droit international privé interne des Etats membres et au delà celles de la discipline du droit international privé elle-même. Toutefois, ce droit international privé, encore en gestation, reste lacunaire dans ses outils et instruments et doit prendre nécessairement appui sur celui des Etats membres comme une nécessité vitale. Either uniform law is seen from the point of view of the private international law or either one assesses the impact of the communal vision of uniform law on the evolution of private international law of member states, the interactions between African uniform law and private international law can all be summed up as follows. A mere unification of laws between some states is not enough to eliminate or solve conflicts of laws and all the difficulties brought about by foreign origin element, such as jurisdiction disputes, foreigners legal status,… The reasons of this situation are that the unification of law (content and procedure rules) has never been total because some indomitable points may prove to be insurmountable at the level of the drafting of uniform rules, but also because the unification of laws can deteriorate further on during its implementation due to various factors. Therefore, the supranational lawmakers have often had to back up the uniform content rules with the uniform rules of private international laws. This leads, in the African uniform law to the emergence of a private international law with a communal origin. The private international law deriving from African uniform law will also be specific in its conception, its methods, its tools or instrument, even if to some extent, it shows some classicism. This is because the private international law deriving from the African uniform law has been fathered by a law which is specific in itself because it stands between international and home law, between public and private law. Its advent has upset the basics of the international home law of member states but also the basics of the private international law itself. However, this private international law which is still in its gestation period still has some weaknesses in its instruments and rules and must necessarily lean on that of member states as it is a vital necessity.
Keywords: Arbitrage international; Conditions des étrangers; Conflict of jurisdictions; Conflict of laws; Conflit de juridictions; Conflit de lois; Droit international privé; Droit uniforme; International Arbitration; Private international law; Right of foreigners; Unification internationale; Uniform law

L'actionnaire de court-terme dans les offres publiques - Jaeglé, Thomas (Université Paris 5, 2013)
Cette thèse vise à analyser les aspects juridiques du rôle joué par les acteurs ayant une stratégie actionariale de court-terme (hedge funds,...) dans le cadre des offres publiques d'acquisition. Outre l'identification de ces acteurs et la description des méthodes employées, il s'agit aussi de s'interroger sur les moyens à disposition de la société cible pour se défendre et de se demander si des évolutions législatives ne seraient pas nécessaires. The purpose of the Phd is to analyze questions raised by short-termism in takevoer bids. As a matter of fact, some shareholders only have short-terme strategies (such as Hedge funds,...) and takeover bids provide some fantastic arbitration opportunities. First, one should clearly identify these actors. Products which might be used in such situation will also have to be studied. Second, one should analyze which defence could provide the target. Third, a study of the opportunity or repealing or amending french legislation on these issues will be done.
Keywords: Actionnaires; Arbitrage; Bourse; Court-termisme; Droit de vote; Hedge Funds; Offres publiques d'achat; Opa; Short-termism; Spéculation; Takeover

Legal aspects of privately financed infrastructure projects (PFIPs) in China: the case for international standards - Liang, Shuang (University of Leeds, 2013)
This thesis discusses the reform and improvement of Chinese legislation on Privately Financed Infrastructure Projects (PFIPs), to develop the PFIP model in China, under the protection of Chinese laws, so that its implementation in China may reach international standards. Existing Chinese laws are found to be insufficient in reducing risks to PFIPs because of certain shortcomings. Therefore, it is necessary to reform and improve Chinese legislation on PFIPs, to prevent their failure. The Legislative Guide and Model Provisions drafted by UNCITRAL are treated as the international standards to guide Chinese legislation reform on PFIPs. Other countries’ laws on PFIPs provide supplementary reference. This thesis addresses its aim in four steps: First, the current Chinese legislative and institutional framework on PFIPs is reviewed, with discussion on establishing a more appropriate legislative and institutional framework, to facilitate the development of PFIPs in China through the principles of transparency, fairness, long-term sustainability and the elimination of undesirable restrictions. Second, Chinese laws on the concessioner selection procedure in PFIPs are reviewed, with discussion on possible improvements to the laws to achieve international standards of fairness and transparency. Third, current Chinese laws and policies which affect the various contracts involved in PFIPs are reviewed, with discussion on these may be improved to achieve international standards. Fourth, the PFIP dispute settlements that may be used in China are reviewed, with discussion on the necessity to remove certain undesirable restrictions in relevant Chinese laws. Following the rapid rise in the practical use of PFIPs in China, this thesis offers a strong theoretical basis for suggesting a reform of Chinese legislation on PFIPs. It also provides a general basis for any national reform of laws on PFIPs in any other countries.

A tutela da confiança nos contratos empresariais - Romero, Anna Paula Berhnes (Universidade de São Paulo, 2013)
O Código Civil, tal como disciplinado atualmente, confere os dispositivos necessários à proteção da confiança, à proibição do comportamento contraditório e demais institutos relacionados à confiança. Para tanto, o direito brasileiro adotou a técnica legislativa da cláusula geral para introduzir em sua normatividade a ética como regra de conduta exigida das partes, cabendo ao Juiz a função integrativa para determinar qual é a conduta adequada em cada caso concreto. Os deveres anexos ou laterais, consagrados pela função criadora de deveres jurídicos da boa-fé objetiva, impõem aos contratantes o cumprimento de obrigações acessórias para que a obrigação principal seja adimplida. A vedação do comportamento contraditório, seu conteúdo, forma de caracterização e aplicação consiste na proteção à confiança e os princípios da dignidade da pessoa humana, da solidariedade e boa-fé objetiva, que norteiam o ordenamento jurídico pátrio. Ao negociar, sabedora das limitações de informações das partes contratos incompletos uma empresa certamente colocará na formação de preços uma parcela que corresponda aos custos da incerteza (riscos) gerados durante as negociações. Ao repensar a situação, e percebendo a oportunidade de eventualmente encontrar o equilíbrio no futuro, poderá a empresa optar por reduzir a parcela de preço decorrente do risco inerente à assimetria de informações, sendo, portanto, mais competitiva ao identificar que eventuais falhas, ainda que inconscientes, podem vir a ser sanadas por meio do provimento judicial. A lealdade que deve presidir as relações entre as partes faz com que os contratos empresariais, dentre outros, residam em ambiente probo, permitindo, assim, o equilíbrio da relação por ocasião das negociações preliminares (culpa in contrahendo), durante a execução do contrato (teoria dos atos próprios - venire contra factum proprium e tu quoque), e após a execução contratual, como ocorre na hipótese da responsabilidade post pactum finitum.
Keywords: Boa-fé; Commercial agreements; Confiance; Contrato comercial; Contrats commerciaux; Direito empresarial; Good faith; Protection; Responsabilidade civil; Trustworthiness

La protection des créanciers au sein des groupes de sociétés - Hmoda, Farag (Université de Franche-Comté, 2013)
L’étude juridique du groupe de sociétés fait apparaître une difficulté majeure qui émane de la grande différence entre le droit et le fait. En effet, bien qu’elles soient liées par un intérêt commun, les sociétés membres d’un groupe ne font toujours pas l’objet d’une réglementation détaillée qui prendrait en considération leur entité et leur unité économique et sociale distinctes. Il découle de cet antagonisme un risque de non correspondance des intérêts particuliers des sociétés membres avec la prévalence juridique de l'intérêt du groupe, lequel pourrait induire des effets préjudiciables aux différentes catégories des créanciers de ces sociétés.Toutefois, cette absence d’une loi particulière aux groupes a donné lieu à une réglementation ponctuelle qui vient modifier des règles du droit des sociétés ou qui régit certains domaines particuliers. De même, en raison d'une telle insuffisance de normes écrites, une importante partie du droit positif des groupes semble d’origine jurisprudentielle. Soutenus par la Cour de cassation, les juges du fond ne cessent de circonscrire les différents aspects de ce phénomène en vue de combler des lacunes juridiques qui heurtent l’équité. Plusieurs théories ont été instaurées en la matière, construisant ensemble une base importante pour la protection des créanciers, des salariés et des associés minoritaires liés à l’ensemble des sociétés regroupées. Legal study of the group of companies reveals a major difficulty which emanates from the big difference between law and reality. Indeed, although they are linked by a common interest, the member companies of a group are not always the object of a detailed ruling which would take into consideration their entity and their economic unity and social distinctions. From this antagonism follows a risk of not connecting the particular member companies with the legal acceptance of the group’s interest, which might lead to prejudicial actions towards the different categories of creditors and companies.However, this absence of a special law for groups gave rise to a timely rule which modifies the rules of the rights of companies or which rules certain particular fields. In the same way, because of an insufficiency of written standards, an important part of the actual right is derived from the origins of precedent. Supported by the Supreme Court of Appeal, the the trial judges do not cease to draw a line around the different aspects of this occurrence in the light of closing a legal loop hole which goes against fairness. Several theories have indeed been established on the subject, forming together an important base for the protection of creditors, wage earners and minor partners linked to the whole of the amalgamated companies.
Keywords: Action to fill in the debit; Conflict of interest; Conflits d'intérêts; Corporate law; Droit des sociétés; Effective director; Extension of joint procedure; Groupe de sociétés; Groupes de sociétés; Mother company; Mère filiale sous-filiale; Obligataires; Protection de créanciers des sociétés filiales; Protection des créanciers internes et externes des filiales; Rapports de contrôle entre sociétés; Redeployment of wage earners; Responsabilité de la société mère; Subsidiary company

Transmission du savoir-faire et contrat de franchise - Al Muhairi, Khamis (Université Paris 1, 2013)
Le contrat de franchise est un contrat d'adhésion qui repose sur la réitération du succès commercial du franchiseur, et qui organise une coopération entre des entreprises indépendantes, D'une part, celle du franchiseur, qui a mis au point et expérimenté un concept substantiel, identifié et réitérable, à même de générer un flux d'activité économique. D'autre part, celle du franchisé, qui adhère au réseau du premier. Il en devient un des maillons, de sorte qu’il bénéficie notamment du savoir-faire. Celui-ci est reconnu comme étant un élément déterminant du contrat de franchise, et qui doit être entendu comme un ensemble secret, substantiel et identifié d’informations pratiques non brevetées, résultant de l'expérience du franchiseur, et testées par celui-ci. Ainsi, dans le cadre d’un contrat de franchise, le franchiseur doit transmettre au franchisé son savoir-faire, qui doit être gardé secret. Le «secret» s’entend du fait que le savoir-faire est difficilement accessible, et sa transmission par le franchiseur conférant au franchisé un avantage concurrentiel significatif. Cet avantage doit se concrétiser par la réussite économique du franchisé, dès lors qu’il respecte les consignes qui lui ont été transmises ; à défaut, sa responsabilité contractuelle pourra être engagée, et pourrait conduire dans certains cas, à l’extinction du contrat de franchise.
Issue: 2013PA010252
Keywords: Competencia; Concessions (commerce de détail); Concurrence; Contract; Contrat; Coopération entre entreprises; Extinction de l'obligation; Franchise; Franchiseur; Franchisor; Obligations; Responsabilité contractuelle; Savoir-faire; Savoir-faire industriel; Secret professionnel; Transmission

Comercio electrónico y pago mediante tarjeta de crédito en el ordenamiento jurídico español : una propuesta para su implementación en el ordenamiento jurídico de Guinea-Bissau - Sanca, Fernandinho Domingos (Universidad Carlos III de Madrid, 2013)
Esta investigación tiene como objetivo determinar la conveniencia de la implementación y el fomento del comercio electrónico en Guinea-Bissau, valorar su viabilidad, identificar los factores que condicionarán esta implantación y proponer un marco regulador adecuado que genere la confianza de los consumidores y proveedores de bienes y servicios. Para acometer este estudio se realiza un extenso análisis doctrinal, jurisprudencial y legal basado sobre todo en el ordenamiento jurídico español y en el derecho comunitario, que nos permitirá proponer un modelo adecuado para Guinea-Bissau. El resultado principal del trabajo es un análisis de la situación jurídica, económica y social en Guinea-Bissau a los efectos de la implantación del comercio electrónico que requiere a su vez el fomento de medios de pago electrónicos, en particular, dadas las condiciones del país y las características comerciales y sociales, de las tarjetas de crédito. De este modo, la investigación pretende concluir con la propuesta de un conjunto de medidas basadas sobre todo en la formulación de disposiciones jurídicas que contribuyan al desarrollo de la sociedad de la información y del comercio electrónico seguro. Además, se propone la reforma del Código Civil y de la Constitución del país, con el objetivo de que se regulen adecuadamente los aspectos relacionados con las nuevas tecnologías de la información y la comunicación y de brindar mayor seguridad jurídica a los entes intervinientes en las operativas de pago mediante tarjeta de crédito en el comercio electrónico. Palabras claves: autenticación y seguridad; medios de pago electrónico; tarjeta de crédito; confianza de consumidores y usuarios; riesgo; uso fraudulento; responsabilidad; comercio electrónico; obligaciones.
Keywords: Carte de crédit; Comercio electrónico; Commerce électronique; Guinea-Bissau; Tarjetas de crédito

Les normes privées relatives à la qualité des produits : étude d’un phénomène juridique transnational - Sarrouf, Muriel (Université Paris 2, 2012)
Les normes privées intéressent le droit international à un double titre : se développant en marge du système interétatique classique, elles constituent l’un des visages d’une régulation privée transnationale émergente et soulèvent la question théorique de leur statut en droit international. Par ailleurs, leurs effets sur le commerce international (et particulièrement le fait qu’elles constituent un obstacle aux exportations des PED vers les marchés occidentaux), conduisent à s’interroger sur l’opportunité et les modalités de leur réglementation par le droit international des échanges. En dépit de leur diversité empirique qui rend difficile toute tentative de systématisation et de qualification juridique, nous considérons que la qualité des produits, qui constitue le fondement téléologique commun des normes privées, permet d’en justifier l’unité théorique et de les considérer comme un phénomène juridique à part entière. Nous démontrerons que les normes privées sont l’une des manifestations d’un droit transnational se développant en parallèle du droit interétatique « classique » et qu’elles jouissent par conséquent d’un statut juridique propre. De ce fait, leurs rapports avec la branche du droit international qu’elles intéressent le plus directement, le droit international des échanges, ne peuvent se limiter à l’approche classique de réglementation (ou approche « répressive », en ce qu’elle a pour seul but d’en limiter les effets restrictifs pour le commerce) mais doivent se concevoir dans une optique de coordination. The recent proliferation of private standards is not only of growing interest to economists who seek to evaluate its impact on trade flows; it is also relevant to international law, particularly to international economic law, in a double perspective. First, from the perspective of legal theory, the legal status of private standards has still to be determined. Second, from an empirical standpoint, private standards have the potential to negatively impact the access of developing countries to the markets of developed countries. This raises the question of the opportunity and modalities of submitting them to the disciplines of the WTO Agreements. This study demonstrates that private standards are one of the expressions of broader ‘transnational law’, a body of law that has been developing in parallel to ‘traditional’ state-centered international law. This implies that international law cannot merely consider private standards as an object to be disciplined; rather, the traditional ‘repressive’ approach should be rejected in favor of a more collaborative approach stressing the interrelations between the two bodies of norms as well as possible forms of coordination.
Keywords: Droit commercial (droit international); Droit transnational; Legal pluralism; Normes privées; OMC; Pluralisme juridique; Private standards; Qualité des produits; Transnational law; WTO

Statutory regulation of forced sale of the home in South Africa - Steyn, Lienne (University of Pretoria, 2012)
The home of a debtor has never enjoyed specific statutory protection against forced sale in the individual debt enforcement and insolvency procedures in South Africa. In Jaftha v Schoeman and Others; Van Rooyen v Stoltz and Others (2005 (2) SA 140 (CC)) and Gundwana v Steko Development CC and Others (2011 (3) SA 608 (CC)), the Constitutional Court recognised that in the individual debt enforcement process execution against a debtor's home, even where it has been mortgaged in favour of a creditor, may constitute an unjustifiable infringement of the right to have access to adequate housing, provided by section 26 of the Constitution. The effect of these decisions is that, in every case in which a creditor seeks to execute against a person's home, a court must consider "all the relevant circumstances" to determine whether execution is justifiable, in terms of section 36 of the Constitution. The absence of a properly constructed framework, incorporating clear substantive and procedural requirements, within which these recently established principles must be applied, has led to divergent approaches in the courts and a lack of clarity regarding circumstances in which execution against a debtor's home will be permitted. Further, courts have not considered the impact of section 26 and other rights on the position where a debtor's home is realised by the trustee of an insolvent estate in terms of the Insolvency Act 24 of 1936. This has given rise to a number of unanswered questions as well as to a lack of predictability that potentially hold adverse consequences for bond finance, commerce, and the economy generally. The need to balance the competing interests emphasises the necessity for a coherent contextual framework within which forced sale of a debtor's home may occur. This thesis examines issues surrounding forced sale of a debtor's home in South Africa. It compares the position in other legal systems and suggests mechanisms and an appropriate method, or process, for inclusion in statutory provisions to regulate the forced sale of a debtor's home in both the individual debt enforcement and insolvency procedures in South Africa.
Keywords: Forced sale; Vente forcée

Contratos de construção de grandes obras - Carmo, Lie Uema do (Universidade de São Paulo, 2012)
A presente tese examina os contratos de construção de grandes obras e a complexidade do seu programa contratual. Contrato de construção em sentido amplo é aquele celebrado entre o proprietário ou dono da obra, como contratante, e uma pessoa física ou jurídica especializada em engenharia ou arquitetura, como contratada, a qual, em contrapartida ao preço, obriga-se à consecução de um ou mais dos seguintes objetos: elaboração do projeto de engenharia ou arquitetura, execução, supervisão, monitoramento e administração da obra, e ainda, se convencionado, prestação de assistência técnica e operação. O exame concentra-se nas construções das categorias industrial e de engenharia, que desenvolvem projetos de porte e enfrentam desafios técnicos, tecnológicos e financeiros elevados, tais como as obras de infraestrutura e de plantas industriais. Por contratos de construção de grandes obras entende-se um gênero (ou categoria) sob o qual pode subsumir-se uma variedade de contratos que tenham por objeto a prestação, mediata ou imediata, de uma obra. Incluem-se nesse gênero contratos típicos, como os de prestação de serviços de engenharia e arquitetura e o de empreitada, e ainda aqueles atípicos, como os de engineering, procurement and construction, project alliancing e project partnering, dentre outros. A tese identifica a estrutura jurídica e as principais características econômico-financeiras de contratos de construção de grandes obras e investiga as fontes da complexidade do seu programa contratual. Reconhecendo-se o contrato de construção de grandes obras como dotado de complexidade, argumenta-se que a complexidade contratual é relevante, com consequências jurídicas, econômicas e sociais que merecem reflexão.
Keywords: BTP; Construction; Construção civil; Contracts; Contrat; Contrato comercial; Contratos; EPC; Empreitada; Engineering; Large projects; Project alliancing; Project partnering

Les contrats internationaux : étude comparative franco-thaïlandaise - Larpvanichar, Ratchaneekorn (Université Lille 2, 2012)
Le droit international privé français des contrats est très avancé, la richesse de la jurisprudence et la doctrine font une bonne preuve de l’évolution du droit français en la matière. Ses conceptions sont répandues et admises par d’autres États, européens en premier lieu, puis dans le monde entier. Le système de droit français et celui de droit communautaire sont complémentaires l’un et l’autre. Pour cette raison l’étude de droit international privé français ne peut plus être restreinte uniquement dans le cadre de droit international commun. Dès lors le droit international privé communautaire devrait aussi faire l’objet de cette étude. Quant au droit international privé des contrats thaïlandais, il est en cours de développement et a besoin de grande réformation urgent pour la coopération juridique dans l’ASEAN. L’étude comparative en cette matière permettrait donc de trouver la bonne solution et d’apprendre l’application de règles conflictuelles ainsi que d’autres mécanismes du droit international privé pour régler les problèmes dans l’ordre juridique thaï. Donc les questions de la loi applicable et le règlement des différends font l’objet principal de cette étude. The French system of Private International Law of Contract is highly developed, evidenced by a rich jurisprudence and doctrinal system. One of the leaders in the field, many of their legal concepts were widely accepted and adopted by other legal systems, first by European countries and then worldwide. However, because of their complementary and intertwined nature for each other, the French legal system cannot be studied apart from the European system. For this reason, this study covers not only an in depth examination of French Private International Law but also a general look at European Private International Law. The Thai system of Private International Law of Contracts, in comparison, is developing and needs significant legal reform, as soon as possible, in order to cooperate with other contracting States in ASEAN. Thus, this comparative study responds to the needs, and shows how to correctly apply the conflict of laws’ rules, including their exceptions, which could solve many problems occurring in the Thai legal system. Therefore questions on the applicable laws of contract and the settlement of disputes which derive from international contract law are objects of this study.
Keywords: Arbitrage commercial international; Choice of Foreign Law; Choice of Forum; Choice of Law; Choice of Transnational Law; Choix de la loi applicable au contrat; Choix de la loi étrangère; Choix de la norme non étatique; Conflict of Jurisdictions; Conflict of laws; Conflit de juridictions; Conflit de lois; Contrats; Contrats internationaux; Droit international privé; Droit international privé français; Droit international privé thaï; Forum shopping; France; Fraude à la loi; French Private International Law; Laws Applicable to Contracts; Lois de police; Lois de police thaïlandaises; Ordre public international; Overriding Mandatory Rules; Public Order; Recherche de la volonté; Thai Overriding Mandatory Rules; Thai Private International Law; Thaïlande

Milletlerarası unsurlu acente ilişkilerinden doğan kanunlar ihtilafı - Güner, Cemil (Selçuk Üniversitesi, 2012)
Milletlerarası ticarette, acenteler aracılığıyla yapılan ticarî işlemlerin önemli bir yeri vardır. Acenteler, tacirler ad ve hesabına sözleşme akdettikleri için, doğrudan temsil hükümleri doğmaktadır. Milletlerarası unsurlu acente ilişkisine uygulanacak hukuk ve bu statünün uygulama alanına giren meselelerin tespiti, kanunlar ihtilâfı hukukunda tartışmalı konulardan biridir. Bu çerçevede, acente ilişkisine uygulanacak hukuk, acente iç ve dış ilişkisi dikkate alınarak tespit edilmektedir. Acente iç ilişkisine uygulanacak hukuk, karşılaştırmalı hukukta ve Türk hukukunda akit statüsüne tâbi tutulmaktadır. Buna göre, acente ve temsil olunan, iç ilişkiye uygulanacak hukuku açıkça ya da zımnen serbestçe seçebilirler. Hukuk seçimi anlaşmasının yokluğunda ise, sözleşmeyle sıkı ilişkili hukuk esas alınır. Sözleşmeyle sıkı ilişkili hukukun tespitinde ise genellikle acentenin işyeri tercih edilmektedir.Acente dış ilişkisine uygulanacak hukuk ise, temsil statüsü olarak anılmaktadır. Buna göre, acente ilişkisinde temsil yetkisine uygulanacak hukuk bakımından, karşılaştırmalı hukukta ve Türk hukukunda, irade muhtariyeti reddedilmektedir. Ancak Avusturya hukuku, İspanyol hukuku ve La Haye Temsil Konvansiyonu'nda sınırlı hukuk seçimine imkân tanıyan düzenlemeler vardır. Milletlerarası acente ilişkisinin gereklerine uygun olarak, temsil olunanın seçtiği hukukun üçüncü kişi tarafından açıkça kabulü şartıyla böyle bir hukuk seçimi geçerli kabul edilebilmelidir. Acente dış ilişkisine uygulanacak hukukun, objektif kriterlere göre tespitinde ise, genellikle acentenin işyeri hukuku tercih edilmektedir. Ancak acentenin işyerinin olmaması ya da üçüncü kişinin bu işyerini bilmemesi hâllerinde, acentenin işyeri hukuku yerine temsil yetkisinin kullanıldığı yer hukukunun bu çerçevede ortaya çıkan ihtilâflara uygulanması kabul edilmektedir. The business transactions are made through agents have important role in the international trade. The direct agency relationship occurs through the agent. Because the agent serves with continuing authority to conclude contract on behalf of and in the name of its? principal. The law applicable to agency relationship with foreign element and finding of it?s application area?s topics are controversial in conflict of laws. In this context, the law applicable to agency relationship is determined according to internal side and external side of this relationship. The internal agency relationship is normally founded on the agency contract and, as such, is governed by the general principles of private international law applying to the contracts in comparative law and Turkish law. According to this, principal and agent may choose expressly or impliedly the law applicable to the internal agency relationship between them. If principal and agent have failed to indicate the law governing, it becomes necessary to determine the law with which the agency contract is most closely connected. In general, this maybe the law of the country in which the agent has his place of business.The law applicable to external agency relationship is known as the agency statute. According to this, the party autonomy has not been adopted as regards the agency statute in comparative law and Turkish law. But there are some exceptional regulations which adopt the resticted party autonomy. For example, Austrian law, Spanish law and, The 1978 Hague Convention on The Law Applicable to Agency allow party autonomy which is resticted. So, the law applicable to external agency relationship may be chosen in accordance with international agency relationship as long as third party expressly adoptes the law principal choices. While the law applicable to external agency relationship is determined in respect of objective criterias, in general, the agent?s place of business is prefered in comparative law like Turkish law. Nonetheless if there is no agent?s place of business or, the third party couldn?t know this place, this matter is governed by the law of place in which the agent act.
Keywords: Acenteler; Agents; Commercial law; Contracts; Hukuki uyuşmazlıklar; Incompatibility; International Law; International disputes; Labour disagrement; Legal disputes; Sözleşmeler; Ticaret; Ticaret hukuku; Trade; Uluslararası Hukuk; Uluslararası uyuşmazlıklar; Uyuşmazlık; İş uyuşmazlıkları

The Business Trust and its role as an entity in the financial environment - Nel, Ebenhaéser Cornelis (Nelson Mandela Metropolitan University, 2012)
The trust figure in South Africa has undergone an interesting process of evolution during the last century – from a mere gratuity or private tax evasion tool to a proper family protection, business entity, investment, and structured finance vehicle. Its flexibility and multi-functionality positioned the trust as an ideal legal institution for many innovative ideas in the search for holistic business structures, economic empowerment transactions, general estate planning and risk protection initiatives, and ultimately, its application as financial instrument and structured finance entity. The development of both traditional and synthetic securitisation schemes in South Africa has been investigated, with some emphasis on the application of the special purpose institution, which may be in trust form. It is submitted that the application of the trust figure has developed without any significant contribution from the local legislator. A sound legal and regulatory framework is crucial for the creation of a strong future environment for legal and financial vehicles. The question is, however, whether the current South African legal framework for the application of the business trust, and also as a vehicle for financial instruments, is adequately sound and robust in light of the standards set in the international business and financial environment. It is submitted that the hybrid nature of the South African legal landscape is conducive for the development of sound legal systems in an ever-changing legal and economic reality. It is further submitted that in the development of proper legal frameworks, South Africa should position itself particularly in its context as a Southern African developing democracy. The South African trust development is compared with that of some foreign jurisdictions as well as with international conventions and treaties of relevance. Some recommendations for necessary changes are made and it is submitted that such future development of the trust figure should not take place haphazardly, but within the context of a structured regulatory model
NMU Archives and Exhibition Centre
Keywords: Asset-backed financing; Corporations; Taxation; Trusts and trustees

Contratos privados da administração pública: uma análise do regime jurídico aplicável - Carvalhaes Neto, Hayden Eduardo (Universidade de São Paulo, 2011)
A celebração de negócios jurídicos é fundamental para a Administração Pública. Sem ela, não só sua interação com a sociedade seria precária, como também não conseguiria cumprir com a maior parte dos princípios que regem seu regime jurídico, pois não se mostra autossuficiente. Para formalizar tais negócios jurídicos, o instrumento utilizado é o contrato. Parte da doutrina defende que tais instrumentos não se enquadram adequadamente no conceito de contrato por conta das peculiaridades que os cingem quando uma das partes pertence à Administração Pública ou está a exercer função que lhe foi delegada pelo Poder Público. De outro lado, aqueles que concordam com a classificação desses instrumentos como contratos dividem-se entre os que acreditam existir um regime jurídico único para todos os contratos da Administração Pública e aqueles que defendem a existência de duas modalidades de contratos: os contratos administrativos, regidos predominantemente pelo direito público, e os contratos privados da Administração Pública, que, tendo como objeto negócios jurídicos característicos da vida privada, são regidos predominantemente pelo direito privado. Somos partidários desta última corrente e, diante da escassa literatura pátria sobre os contratos privados da Administração Pública, nos propomos a analisá-los mais detidamente no presente estudo. Assim, dividimos este trabalho em cinco capítulos. No primeiro deles, apresentaremos nossas considerações iniciais sobre a matéria, fornecendo um apanhado do que a doutrina nacional e estrangeira já produziu sobre o assunto e de como se dividem as opiniões. Tendo em vista que os contratos regidos primordialmente pelo direito privado apresentam grande parte dos traços dos contratos privados, no segundo capítulo analisaremos as características mais relevantes das cláusulas típicas de direito público que integram os contratos administrativos. O terceiro capítulo, por sua vez, é dedicado à verificação da legislação brasileira e os respectivos dispositivos normativos pertinentes aos contratos privados da Administração Pública. No quarto capítulo nos debruçaremos sobre as decisões jurisprudenciais estrangeiras que marcaram o início da distinção entre as duas modalidades de contratos da Administração Pública e no quinto capítulo apresentaremos nossas conclusões, conjuntamente com algumas sugestões que acreditamos sejam pertinentes ao aperfeiçoamento do tratamento da matéria no Brasil. The execution of legal businesses is essential for the Public Administration. Without it, not only its interaction with society would be precarious, but also could not comply with most of the principles governing their legal regime, as it is not show selfsufficient. In order to formalize such legal transactions, the instrument to used is the agreement. Part of the doctrine sustains that such instruments do not fit properly on the concept of agreement because of its peculiarities when one of the parties belongs to the Public Administration or is exercising function that has been delegated by the Public Power. On the other hand, those who agree with the classification of such instruments as agreements are divided between those who believe that there is a single legal regime for all the agreements executed by the Public Administration and those who advocate the existence of two "modalities" of agreements: the administrative agreements, predominantly governed by public law, and private agreements of the Public Administration, which having as subject legal businesses that are typical of the private life, are governed mainly by private law. We agree with this latter view, and because of the scarce literature on private agreements of the Public Administration, we propose to examine them more closely in this study. We have divided this paper into five chapters. In the first one, we will present our initial thoughts on the subject, providing an overview of what the national and foreign doctrine has produced on the subject and how the opinions are divided. Given that agreements governed by private law primarily present most of the characteristics of private agreements, in the second chapter we will analyze the most relevant characteristics of the typical clauses that integrate the administrative agreements. The third chapter, on its turn, is devoted to the verification of the Brazilian legislation and the respective applicable normative provisions pertaining to the private agreements of the Public Administration. In the fourth chapter we will lean over the foreign court decisions that became the landmarks of the beginning of the distinction between the two modalities of agreements of the Public Administration and in the fifth chapter we will present our findings, together with some suggestions that we believe are relevant to improving the handling of this matter in Brazil
Les contrats privés dans l'administration publique : une analyse du cadre juridique applicable
Keywords: Administrative agreements; Administrative law; Administração publica; Agreements; BID; Contrato administrativo; Exorbitant clauses; Legal business; Licitação; Prerogatives; Private agreements; Public administration

Dynamiques paysannes, souveraineté alimentaire et marché mondial des produits agricoles : exemple du Sénégal - Diop, Amadou Makhourédia (Institut National Polytechnique de Toulouse, 2011)
Comme dans presque tous les pays d'Afrique subsaharienne, la majorité de la population sénégalaise est rurale. Elle vit de l'agriculture ou d'activités qui en dépendent. Paradoxalement les investissements publics dans le secteur agricole restent très faibles, alors que l'insécurité alimentaire progresse. Pour faire face aux problèmes alimentaires, les pouvoirs publics multiplient les annonces de politiques agricoles, qui ne sont presque jamais suivies d'effets, parce que ne reposant pas sur des études précises et rigoureuses. Dans ce contexte, nous avons cherché à comprendre les stratégies développées par la petite paysannerie, les dynamiques qui animent les exploitations agricoles familiales pour faire reculer l'insécurité alimentaire en milieu rural, et dans quelle mesure celles-ci peuvent contribuer à la souveraineté alimentaire du Sénégal. Cette question appelle celle de l'accès à une nourriture suffisante et celle de sa production. Ainsi, à travers notre étude que nous avons intitulée « Dynamiques paysannes, souveraineté alimentaire et marché mondial des produits agricoles : l'exemple du Sénégal », nous cherchons à répondre à une série de questions : 1. Comment les paysans sénégalais produisent-ils les biens nécessaires à l'alimentation et l'entretien de leur famille ? 2. Comment les paysans sénégalais sont-ils organisés autour des questions de la vie rurale ? 3. Quelle est l'influence du marché mondial de produits agricoles et de ses règles établies par l'Organisation mondiale du commerce (OMC), sur la disponibilité et l'accès aux produits alimentaires ? De quelle façon les biens alimentaires importés concurrencent-ils la culture de biens agricoles qu'il est possible de produire localement ? Nous avons ainsi consacré une première partie de notre étude au procès de production et à son évolution. En dehors des conditions climatiques, le contrôle effectif par les paysans, des moyens de production et de la tenure foncière, détermine en grande partie, les volumes de biens agricoles et alimentaires produits, ainsi que leur accès. Dans une seconde partie, nous avons analysé l'émergence et l'évolution des modes d'organisation paysanne et examiné leur influence sur la satisfaction des besoins alimentaires et les orientations des politiques publiques en matière agricole. Enfin, dans une troisième partie, nous avons essayé de mesurer l'impact des règles du commerce international sur les productions locales de biens agricoles et alimentaires. Ce travail nous a permis de tirer un certain nombre de conclusions. La majorité des paysans du Sénégal ne parvient plus à produire le volume d'aliments de base nécessaires pour nourrir et entretenir leur famille. Les moyens de production ont relativement peu évolué au cours des dernières décennies, même si la culture attelée et l'introduction de nouveaux matériels ont considérablement amélioré les conditions de production et diminué la pénibilité du travail. L'outil de production s'est dégradé et ce qu'il en reste ne survit que grâce à l'habileté des forgerons ruraux. La recherche agronomique a permis d'obtenir des variétés homologuées de semences adaptées aux conditions pédologiques et climatiques. Mais elle demeure inefficace en ce sens que les moyens pour appliquer concrètement ses résultats sont absents et les paysans n'ont aucune maîtrise sur elle. Sur le plan du commerce international des produits agricoles, la faiblesse du Tarif extérieur commun (TEC) de la CEDEAO a eu pour conséquence l'augmentation des volumes d'importations de biens qui peuvent être produits localement. Les règles de l'OMC basées sur une conception ultralibérale du marché portent davantage préjudice aux produits agricoles et alimentaires de l'Afrique de l'Ouest. Sur un plan plus global, et à défaut de sortir l'agriculture des accords de l'OMC, il est possible de réclamer avec la CEDEAO, la mise en place d'un autre Accord sur l'agriculture qui redéfinirait le dumping de manière à protéger les pays les plus vulnérables. As in almost all SSA countries, the majority of the Senegalese population is rural. They earn their livelihoods from agriculture or activities that depend on it. Paradoxically, the public investment in agriculture remains very low, while food insecurity is progressing. To deal with food problems, the government multiplies announcements of agricultural policies, which are almost never followed up, because not based on specific and rigorous studies. Instead of policies, there are mostly management strategies cyclical food crises. In this context, we have sought to understand the strategies developed by the peasantry, the dynamics that drive family farms to reduce food insecurity in rural areas, and to what extent they can contribute to food sovereignty Senegal. This question calls for that of access to adequate food and that of its production. Thus, through our study we have entitled "Farming dynamics, food sovereignty and global market for agricultural products: the example of Senegal”, we try to answer a series of questions: 1. How do Senegalese farmers produce the goods needed to feed and care for their family? 2. How are Senegalese farmers organized around issues of rural life? 3. What is the influence of the world market of agricultural products and its rules established by the World Trade Organization (WTO) on the availability of and access to food? How do imported goods compete with food products that can be produced locally? We have devoted the first part of our study to the production process and its evolution. Apart from weather conditions, effective control by farmers of means of production and land tenure, largely determines the volumes of agricultural and food products as well as their access. The second part analyzes the emergence and evolution of modes of peasant organization and discusses their influence on the satisfaction of food needs and directions of public policy in agriculture. Finally, in the third part, we have tried to measure the impact of international trade rules on local production of agricultural goods and foodstuffs. This work has enabled us to draw some conclusions. The majority of farmers in Senegal can no longer produce the amount of basic foods needed to feed and support their families. The means of production have changed relatively little in recent decades. The production tool has deteriorated and what is left survives only thanks to the ability of rural blacksmiths. Research in agriculture has yielded certified seed varieties adapted to soil and climatic conditions. But it remains ineffective in that the means for concretely applying its results are absent and the peasants have no control over it. The question of land remains subject to trial and error due to its complexity, traditional beliefs and practices in this area do not yet seem ready to give way to modern rules, or if necessary, adapt to them. More and more severe conditions felt primarily in the food sector have highlighted the capacity of the peasantry to adapt. For each new situation causing additional problems, novel solutions are devised and implemented by farmers, enabling them to adapt in an unexpected manner. Farmers' ability to take charge of their own concerns were highlighted by the emergence of organizations, groups, associations and unions throughout the rural areas of Senegal. As far as international trade in agricultural products is concerned, the weakness of the Common External Tariff (CET) of ECOWAS has resulted in increased volumes of imports of goods that can be produced locally. WTO rules, based on an ultra-liberal conception of the market, are more detrimental to West African agricultural and food products. More globally, unless agriculture is removed from WTO agreements, it is possible to claim with ECOWAS, the implementation of another agreement on agriculture that would redefine dumping so as to protect the most vulnerable countries.
Keywords: Agricultural policy; Exploitation familiale; Family farms; Food security; Land tenure; Marchés agricoles; Market of agricultural products; Organisations paysannes; Peasant organizations; Politique agricole; Sécurité alimentaire; Tenure foncière

Hukuk sosyolojisi açısından vahiy döneminde ticari hayat - Baysa, Hüseyin (Ondokuz Mayıs Üniversitesi, 2011)
Modern dönemde ticarî hayatta ortaya çıkan mübadele yöntemlerini İslâm ticaret hukuku açısından değerlendirebilmek ve İslâm'ın ticarî alandaki temel ilkelerine aykırı işlemlere alternatif yöntemler üretebilmek için öncelikle vahiy dönemindeki ticaret hukukunu tespit etmek gerekmektedir. Vahiy dönemindeki ticaret hukukunun sağlıklı bir şekilde anlaşılabilmesi ise dönemin ticarî kurallarının sosyolojik açıdan incelenmesini zorunlu kılmaktadır. Bu amaçla yapılan bu araştırmada ulaşılan sonuçları kısaca şu şekilde ifade etmek mümkündür:Cahiliye döneminde Hicaz bölgesinde sosyal hayat, bölgenin coğrafî yapısı ile dönemin siyasî ve dinî şartları etkisi altında sürdürülmüştür. Yeni bir yaşam biçiminin hedeflendiği vahiy döneminde toplumsal hayatın bütün ünitelerinde değişikliğe gidilmiş, Hicazlılar'ın iktisadî tecrübe ve ihtiyaçları göz önünde bulundurularak yeni bir ticaret hukuku oluşturulmuştur. Mekke devrinde, Hz. Peygamber kanun koyup uygulayacak siyasî güce sahip olmadığı için, hayatın diğer alanlarında olduğu gibi ticaret hukuku alanında da temel ahlâkî değerler müslüman tebaaya benimsetilmeye çalışılmakla yetinilmiştir. Hicretten sonra Medine'de siyasî ve askerî bakımdan yeterli güce kavuşulunca ekonomik sisteme müdahale edilmeye başlanmıştır. Bir önceki dönemden devralınan ticarî kurum ve işlemler adalet eksenli yeni hukukî ve ahlâkî kurallara göre değerlendirilmeye tabi tutulmuştur. Ticaret hayatında yapılan değişiklikler içtimaî kurallara uygun bir şekilde gerçekleştirilmiştir. Yeni hukukî düzenlemelerin kargaşaya meydan vermemesi için gerekli görülen konularda tedricî yöntem uygulanmış ve alternatif uygulamalar devreye sokulmuştur. Öte yandan toplumsal yapıyı oluşturan diğer kurumlarda gerçekleştirilen değişiklikler de yeni ticaret hukukunun kolaylıkla topluma mal edilmesinde oldukça etkili olmuştur. Occurring in the commercial life of modern methods of exchange, to assess in terms of commercial law of Islam, and contrary to the fundamental principles of commercial transactions in the field of Islam in order to produce alternative methods, primarily trade law to determine the required period of revelation. Revelation during the period of commercial law in a healthy way to understand the rules of trade requires a review of the sociological perspective. For this purpose, the results achieved in this study, it is possible to briefly stated as follows:The period of ignorance of social life in the Hijaz, the region's geographical structure and the period continued under the influence of political and religious conditions. Revelation in a new way of life, social life aimed to change all the units were made, considering the economic needs of the people of Hijaz experience and created a new trade law. Mecca during the reign of the Prophet put the law does not have the power to implement the political, as in other areas of life in the field of commercial law to teach basic moral values were muslims. After the migration, the strength is reached Medina, the political and military respects, the economic system started to intervene. Commercial institutions and processes inherited from the previous period, according to the rules of justice-oriented evaluation has been subject to new legal and moral. Changes to trade in his life was carried out in accordance with social rules. New legal challenge to prevent confusion in the arrangements, gradual method is applied to matters deemed necessary and alternative practices were introduced. On the other hand, changes in social structure in the new trade law is easily performed by other institutions in society to be the goods have been quite effective.
Keywords: Cahiliye Dönemi; Commercial law; Commercial life; Hedjaz; Hicaz; Hukuk sosyolojisi; Islam; Jahiliyye Period; Law sociology; Socio-cultural structure; Socio-economic life; Sosyoekonomik hayat; Sosyokültürel yapı; Ticaret; Ticaret hukuku; Ticari hayat; Trade; İslamiyet

South African anti-dumping law and practice : a juridical and comparative analysis of procedural and substantive issues - Sibanda, Omphemetse Stephen (North-West University, 2011)
This thesis addresses issues of anti-dumping law and practice from a critical and juridical analysis position. In particular, the thesis seeks to determine whether the South African anti-dumping regime is compliant with the anti-dumping regime of the World Trade Organization (hereafter WTO), and to consider possible solutions for addressing instances where the South African law is not WTO compatible. The thesis departs from the hypothesis that the WTO merely requires functional equivalence of the implementation of national legislation on anti-dumping, and not the verbatim adoption of WTO jurisprudence and relevant provisions of the Agreement on the Implementation of Article VI of the General Agreement on Tariffs and Trade of 1994 (hereafter URAA), into the legislation of State Parties. Some of the provisions of the URAA are not completely clear, and are cast in convoluted and complicated technical jargon, leaving loopholes that may be justifiably exploited by State Parties. The study in this thesis was achieved through the critical analysis of legislation and relevant legal documents, case law and contemporary literature. The primary research paradigm used in this study is interpretive and analytical, which is the same as qualitative research methodology. The legal comparative research method, with a historical component, also played an important role in this study. The literature study undertaken and the critical analyses made of the South African anti-dumping regime show mixed findings. The South African antidumping regime was found to have both positive aspects and problematic aspects when compared with WTO regulations. Some of the critical areas of the South African anti-dumping regime are WTO compatible whilst others are not. In some areas the South African anti-dumping regime has adopted functionally equivalent provisions to the provisions of the WTO law. However, the practice of the International Trade Administration Commission (ITAC) is sometimes fraught with inconsistencies. The compatibility of the South African anti-dumping system with the WTO regime came close to being examined by the WTO on 1 April 1999 in the dispute of South Africa - Anti-dumping Duties on the Import of Certain Pharmaceutical Products from India based on allegations that the method for calculating normal value used by the ITAC was found to be inconsistent with the URAA. Similarly, the conformity of the procedures and findings of the International Trade and Administration Act (ITAA) in anti-dumping cases came under attack in the cases of Algorax v The International Trade Administration Commission and others, and Scaw v The International Trade Administration Commission and others, respectively. Finally, the thesis ends with recommendations in response to the challenges identified and key submissions made throughout the analysis. Key recommendations include the broadening of the concept of interested parties to include registered trade unions and trade union federations; introducing an explicit and mandatory "public Interests" provision to ensure that South Africa's anti-dumping administration is free from political trappings in the form of the involvement of the Minister of Trade and Industry; introducing the new section 31 bis of the ADR in order to allow the initiation of anti-dumping petitions by a registered trade union or trade union federation; providing procedural guidelines for self-initiation of anti-dumping petitions by the ITAC; increasing transparency in anti-dumping proceedings and enquires; setting realistic time-lines for all anti-dumping processes and ensuring compliance with the same; improving the institutional and functional capacity of the ITAC; amending section 18.3 of the ADR to allow search and seizure operations pursuant to the provisions of the Criminal Procedure Act 51 of 1977 and the Customs Act; having a clear provision on verification visits confidentiality and a clear provision on producer knowledge; introducing a clear provision in the ADR dealing explicitly with zeroing pursuant to Article 2.4.3 (ii) of URAA; and the introduction of duty refund procedures. It is hoped that the recommendations made in this thesis, which are in the form of suggested legislative interventions required to upgrade certain areas of South African anti-dumping law and practice to be fully WTO compliant, will influence the introduction of suitably crafted anti-dumping legislation in South Africa. It is further hoped that the thesis will become an invaluable source of information for practitioners and students, and a critical source on the best practice for the imposition and implementation of anti-dumping measures. Moreover, the thesis will add to the body of academic writing on South African anti-dumping law.
Keywords: Antidumping duties; Dumping (International trade); South Africa

A auditoria externa e as demonstrações contábeis no direito comercial - Pereira, Alexandre Demetrius (Universidade de São Paulo, 2010)
A auditoria externa de demonstrações contábeis é um dos instrumentos mais importantes para o desenvolvimento do mercado, pelo fato de adicionar credibilidade e segurança às informações financeiras prestadas pelos agentes econômicos que buscam captar recursos junto ao público investidor. A doutrina jurídica pátria, entretanto, ao contrário do que ocorre em outros países, tem relegado o estudo do assunto a um papel secundário, quase não abordado nas obras nacionais, deixando sua pormenorização integralmente sob o domínio da ciência contábil. Esta postura causa um afastamento do jurista da realidade das circunstâncias em que a auditoria se desenvolve, fazendo com que, pela falta de compreensão das peculiaridades da matéria, haja a aplicação inadequada de muitos institutos a uma realidade específica e, muitas vezes, diversa daquela para as quais referidos institutos foram concebidos. Como a matéria abrange tanto o Direito quanto a Contabilidade, tencionamos fazer aqui uma abordagem conjunta, a fim de possibilitar a comunicação das duas ciências e compartilhar os problemas que o tema apresenta. Passamos em revista a natureza dos principais institutos de auditoria; seu relacionamento e importância na economia; as características jurídicas do contrato, suas obrigações, as partes contratantes e os terceiros interessados; o desenvolvimento contábil de sua execução; e seu relacionamento com os sistemas de governança corporativa. Além disso, verificamos as atuais tendências quanto ao sistema de riscos e responsabilidade civil do auditor, matéria amplamente discutida no âmbito internacional.
Keywords: Accounting and legal repercussions; Audit contract; Audit externe; Auditoria; Auditoria externa; Auditors liability; Balance comptable; Balanço contábil; Comptabilité; Contratos; Demonstração financeira; Direito comercial; Droit commercial; Etat financier; External audit; Governança corporativa; Responsabilidade civil; Responsabilité de l'auditeur

Teoria palco-platéia: a interação entre regulação e autorregulação do mercado de bolsa - Calabró, Luiz Felipe Amaral (Universidade de São Paulo, 2010)
A tese a ser defendida é a de que a autorregulação institucionalmente estruturada e legitimada pela regulação é um eficiente arranjo para tratar as falhas e riscos inerentes ao mercado de bolsa. O trabalho se inicia com a descrição da atual estrutura da autorregulação do mercado de bolsa, destacando seu novo formato institucional decorrente do processo de desmutualização e abertura de capital das entidades administradoras do mercado de bolsa e concluindo pela necessidade de adoção de novas perspectivas sobre o tema que transcendam o aparente antagonismo entre concepções liberais e intervencionistas. A partir dessa premissa, o trabalho apresenta uma visão panorâmica da evolução histórica da autorregulação do mercado de bolsa e considerações sobre os conceitos de autorregulação em outras áreas do conhecimento, a fim de identificar suas variações e seus elementos mais marcantes que constituirão a base a partir da qual serão apresentadas as novas perspectivas de análise do tema. As perspectivas propostas enfocam a natureza jurídica da autorregulação do mercado de bolsa como atividade paraestatal destinada a concretizar o modelo teórico neoclássico de justa formação dos preços segundo a livre atuação das forças de oferta e demanda e, também, melhorar os padrões de conduta praticados no mercado. Para tanto, o trabalho propõe que as decisões tomadas no âmbito da autorregulação se pautem por critérios materiais baseados nas premissas teóricas da concorrência perfeita e na exigência de cumprimento dos deveres derivados da boa-fé objetiva (informação, lealdade e proteção). Por fim, é apresentada uma especulação teórica, preliminar e não definitiva, denominada teoria palco-platéia, que visa situar o desenvolvimento da estrutura de autorregulação do mercado de bolsa como parte de uma questão essencial de interação entre indivíduo e sociedade representada nas diversas situações comunicativas envolvidas nos processos decisórios individuais e coletivos que modelam os padrões de conduta e as instituições públicas e privadas.
Keywords: Autorégulation; Bolsa de valores; Direito comercial; Equities; Exchange market; Marché boursier; Mercado de capitais; Mercado futuro; Regulation; Régulation; SRO; Securities; Self-regulation; Self-regulatory organizations; Stage-audience; Stock Exchange

A critical evaluation of the interaction between sport and law in South Africa - Louw, André Mouton (Stellenbosch University, 2010)
This dissertation contains an evaluation of the interaction between law and sport in South Africa. The evaluation includes description of the main areas where laws (in the form of the common law, legislation and the relevant provisions of the Constitution of the Republic of South Africa, 1996) apply to sport, in the contexts of both amateur sport and the fast-developing professional sports industry. Apart from such descriptive content, the dissertation will also critically evaluate the appropriateness of the relevant laws and their application in the often atypical context of sport, as well as the courts' treatment of the relevant legal issues. In the process of providing such critical evaluation, and where relevant, the author includes a comparative analysis of the treatment of relevant legal issues in other jurisdictions (most notably the United Kingdom and European Union, which are especially relevant in light of the application of the 'European model' of sports governance and regulation, which applies to the major sporting codes in South Africa). In particular, the author critically evaluates the following aspects of the South African jurisdiction's treatment of the application of law to sport: - The South African system of public regulation of sport by the State (and, specifically, the issue of the race-based transformation of sport, which involves an apparent government-driven agenda and is unique to the South African jurisdiction); - The courts' treatment to date of the susceptibility of the conduct of sports governing bodies to judicial scrutiny (and of the nature of such bodies as voluntary associations); - Various aspects related to the application of employment laws to the employment of professional athletes in team sports; - The application of common law remedies for breach of contract in the professional sports employment context; - The potential application of the restraint of trade doctrine (in, as the author suggests, an extended_ form) in the context of the freedom of movement of professional athletes; The apparently unsatisfactory state of current South African law in respect of legal protection against commercial misappropriation of aspects of the persona of famous athletes (i.e. in the context of 'image' -or-,'publicity' rights as recognized in certain other jurisdictions); and - An evaluation of the extensive protection (especially in the form of specific legislation in South Africa) against ambush marketing of major sporting events. The author includes some concluding observations regarding the state of South African sports law as compared to other jurisdictions, as well as some comment on expectations for the future development and potential importance of the South African domestic jurisdiction in the application of law to sport.
URI: http://hdl.handle.net/10019.1/49490 There are three other contributors to this work numbering 15 p. in total.
Keywords: Comparative law; European Union; South Africa; Sports; United Kingdom

Business law transplants and economic development: an empirical study of contract enforcement in Dakar, Senegal - Paquin, Julie (McGill University, 2010)
La création d'environnements attrayants pour les investisseurs est récemment devenu une priorité pour les spécialistes du développement, qui conseillent aux pays en voie de développement d'adopter les « meilleures pratiques » d'affaires utilisés dans les pays développés. Bien qu'on reconnaisse que le transfert de modèles juridiques d'un pays à un autre entraîne souvent des résultats décevants, la question du niveau de compatibilité requis entre les modèles transférés et le pays importateur est le plus souvent ignorée ou considérée comme une question technique relevant de la compétence des professionnels du droit locaux. Dans ce processus, pratiquement aucune place n'est faite au point de vue des utilisateurs finaux des nouvelles normes et institutions. La présente thèse se fonde sur une étude empirique de l'impact de la réforme du droit des affaires relativement en matière d'exécution des contrats. Dans une première partie, les hypothèses sur lesquelles les réformes actuelles se fondent sont examinées à la lumière de contributions provenant de divers champs disciplinaires. Divers facteurs considérés comme expliquant les effets limités des réformes entreprises jusqu'à présent sont présentés. La deuxième partie analyse le contenu de 30 entretiens en profondeur réalisés auprès de petites et moyennes entreprises de Dakar, Sénégal. Les entretiens révèlent que les PMEs dakaroises font preuve d'une grande flexibilité dans l'exécution de leurs contrats d'affaires, et que la qualité des institutions juridiques et judiciaires joue un rôle peu important dans les décisions qu'ils prennent à cet égard. L'environnement général dans lequel elles opèrent, qui se caractérise par la présence de contraintes financières importantes, un haut niveau d'inceritude et une grande interdépendance entre les entreprises, constitue le facteur le plus important pour expliquer le comportement des entreprises. La troisième part
https://escholarship.mcgill.ca/concern/theses/gm80hv75c
Keywords: Business law; Contract enforcement; Economic development; Senegal